Fiber treatment agent
Patent Information
- Application Number
- JP2021207574
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-12-25
- Filing Date
- 2021-12-21
- Publication Date
- 2024-12-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Regenerated collagen fibers used in head ornaments suffer from high water absorption leading to reduced mechanical strength, low heat resistance, and lack of thermal shape memory, limiting their suitability and styling freedom compared to synthetic fibers.
A fiber treatment agent comprising a condensate of formaldehyde or its hydrate and a triazine derivative is used to treat naturally-derived fibers, maintaining a turbidity of 1000 NTU or less, which improves water resistance, heat resistance, and imparts thermal shape memory while enhancing stretchability.
The treated fibers exhibit improved mechanical strength, heat resistance, and thermal shape memory, comparable to human hair, with enhanced stretchability and texture, making them suitable for head ornaments.
Smart Images

Figure 2022103111000001 
Figure 2022103111000002 
Figure 2022103111000003
Abstract
Description
[Technical Field]
[0001] The present invention relates to a fiber treatment agent for imparting water resistance, heat resistance, and thermal shape memory ability to natural fibers used in headwear products such as wigs and extensions. [Background technology]
[0002] Naturally derived fibers have applications such as wigs and hair extensions, and unlike synthetic fibers, they possess a natural texture and appearance derived from natural materials. Among naturally derived fibers, regenerated protein fibers, such as regenerated collagen fibers, are obtained by solubilizing acid-soluble or insoluble collagen with alkali or enzymes to create a spinning solution, which is then extruded through a spinning nozzle into a coagulation bath to form fibers.
[0003] However, regenerated collagen fibers generally have higher hydrophilicity than synthetic fibers, resulting in a high water absorption rate and extremely low mechanical strength when saturated with water. Therefore, during shampooing, the high water absorption rate significantly reduces mechanical strength, leading to breakage during subsequent drying with a hairdryer, thus reducing their suitability as headwear products.
[0004] Furthermore, regenerated collagen fibers have a problem with low heat resistance. When styling with a hair iron, if they are styled at the same high temperatures as human hair, they will shrink and become frizzy, spoiling their appearance.
[0005] Furthermore, while plastic synthetic fibers retain their shape after heat styling with a hair iron, etc., even after subsequent washing (they have thermal shape memory), regenerated collagen fibers lose their shape after heat styling with a hair iron, etc., after subsequent washing (they lack thermal shape memory). Therefore, they are inferior to conventional plastic synthetic fibers in terms of styling flexibility.
[0006] The three points described above have been factors hindering the spread of regenerated collagen fibers for use in headdress products. In particular, the influence of water resistance, that is, the decrease in mechanical strength when wet, was significant. Therefore, in order to modify regenerated collagen fibers and impart water resistance and heat resistance, attempts have been made to act reactive substances on the amino groups possessed by collagen molecules, and as an example, a method of acting a compound having a methylol group is known (Patent Documents 1 and 2). Also, in the field of human hair fibers, which are also used in headdress products, a method of acting a compound having a methylol group to newly impart heat shape memory ability to human hair fibers that originally do not have heat shape memory ability is known (Patent Document 3).
Prior Art Documents
Patent Documents
[0007]
Patent Document 1
Patent Document 2
Patent Document 3
Summary of the Invention
Problems to be Solved by the Invention
[0008] However, in the manufacturing scene of headdress products, the fibers may be strongly stretched, and in the techniques described in Patent Documents 1 to 3, the elasticity (tenacity) of the treated fibers may not be sufficient. Therefore, in order to prevent breakage during stretching, there has been a demand to enhance the elasticity of the treated fibers.
[0009] Therefore, the present invention relates to a fiber treatment agent for producing fibers for headdress products in which the water resistance and heat resistance of natural-derived fibers represented by regenerated collagen fibers are improved, heat shape memory ability is imparted, and elasticity (tenacity) is also excellent.
Means for Solving the Problems
[0010] The inventors have discovered that when the fiber treatment agents described in Patent Documents 1 to 3 are treated according to the fiber treatment methods described in those documents, the composition in which the fibers are immersed undergoes a transformation through three phases. Specifically, in Phase 1, the composition contains formaldehyde and melamine derivatives in a mutually free reaction, resulting in high turbidity. In Phase 2, the formaldehyde and melamine derivatives react to form water-soluble condensates, causing the composition to become transparent. In Phase 3, the water-soluble condensates further link together to form water-insoluble condensates, and the turbidity of the composition increases again.
[0011] The inventors found that when natural fibers are brought into contact with the Phase 1 composition, the free formaldehyde directly acts on the fibers, crosslinking the tissue and making it difficult to maintain their elasticity (toughness). On the other hand, they also found that when fibers are brought into contact with the Phase 3 composition, a hard resin layer is formed on the surface of the fibers, restricting their bending and stretching movements, making it difficult to maintain their elasticity (toughness), and furthermore, the feel of the fiber surface deteriorates.
[0012] Based on the above findings, the inventors furthered their research and discovered that by treating naturally derived fibers with a composition containing a condensate of formaldehyde and a specific triazine derivative with a turbidity of 1000 or less, while maintaining the turbidity of the treatment agent at 1000 NTU or less, the water resistance and heat resistance of the naturally derived fibers are improved, and thermal shape memory is imparted. Furthermore, surprisingly, the elasticity (toughness) of the fibers is improved compared to before treatment, reaching a level close to that of human hair, and the feel of the fiber surface is also improved. Thus, the inventors completed the invention. Normally, compounds containing methylol groups, such as those used in references 1-3, crosslink the tissue, so it is common knowledge that the tissue becomes brittle after treatment. However, it is surprising that, under the above conditions, when natural derived fibers were treated, the elasticity (toughness) was improved compared to before treatment.
[0013] The present invention provides a fiber treatment agent containing a condensate formed from the following components (A) and (B), and component (C), wherein the total content of components derived from component (A) and components derived from component (B) exceeds 1% by mass, and the turbidity is 1000 NTU or less. (A): Formaldehyde or its hydrate (B): Triazine derivative represented by general formula (1)
[0014] [ka]
[0015] [In the formula, R 1 ~R 3 These may be the same or different and represent a hydrogen atom, a hydroxymethylamino group, an amino group, a hydroxyl group, a halogen atom, a phenyl group, a linear or branched alkyl or alkenyl group having 1 to 6 carbon atoms, or a linear or branched alkoxy or alkenyloxy group having 1 to 6 carbon atoms. (C):Water
[0016] Furthermore, the present invention provides a method for producing a fiber treatment agent, comprising heating a composition containing the above components (A) to (C), wherein the total content of components derived from component (A) and components derived from component (B) is 1% by mass or more, until the turbidity becomes 1000 NTU or less.
[0017] Furthermore, the present invention provides a fiber processing method comprising the following step (i). (i) A process of immersing the fibers in the fiber treatment agent and treating them while maintaining the turbidity of the treatment agent to 1000 NTU or less.
[0018] Furthermore, the present invention provides a method for manufacturing fibers for headwear products, which includes a step of processing the fibers using the fiber processing method described above.
[0019] Furthermore, the present invention provides a method for manufacturing a headwear product, which includes a step of processing the fibers using the aforementioned fiber processing method.
[0020] Furthermore, the present invention provides a fiber for headwear products containing a condensate produced from the above components (A) and (B).
[0021] Furthermore, the present invention provides a headwear product comprising fibers containing a condensate produced from the above-mentioned components (A) and (B). [Effects of the Invention]
[0022] According to the present invention, it is possible to provide a fiber treatment agent for manufacturing fibers for headwear products that have improved water resistance and heat resistance, are given thermal shape memory ability, and have improved elasticity (toughness) of naturally derived fibers. [Modes for carrying out the invention]
[0023] [Fibers to be processed in this invention] The fibers to be treated with the fiber treatment agent of the present invention may be either synthetic fibers or naturally derived fibers, but naturally derived fibers are preferred. Naturally derived fibers refer to fibers collected from natural plants and animals, or fibers artificially manufactured using keratin, collagen, casein, soybeans, peanuts, corn, silk waste, silk fibroin, etc. as raw materials, and are used in the manufacture of headwear products. Of these, fibers artificially manufactured using keratin, collagen, casein, soybeans, peanuts, corn, silk waste, silk fibroin, etc. as raw materials are preferred, regenerated protein fibers such as regenerated collagen fibers made from collagen and regenerated silk fibers made from silk fibroin are more preferred, and regenerated collagen fibers are even more preferred.
[0024] Regenerated collagen fibers can be manufactured using known technologies, and their composition does not need to be 100% collagen; they may contain natural or synthetic polymers or additives for quality improvement. Furthermore, they may be post-processed regenerated collagen fibers. The preferred form of regenerated collagen fibers is filament. Filaments are generally removed from bobbins or boxes. Alternatively, filaments that come out of the drying process during the manufacturing of regenerated collagen fibers can be used directly.
[0025] [Condensate formed from components (A) and (B)] The fiber treatment agent of the present invention contains a condensate of formaldehyde or its hydrate, component (A), and a triazine derivative represented by general formula (1), component (B). In addition to the water-soluble condensate described above, this condensate may also include water-insoluble condensates formed by further linking of water-soluble condensates, provided that the turbidity of the fiber treatment agent is 1000 NTU or less. In this specification, when simply referred to as "condensate," it includes both water-soluble and water-insoluble condensates. Furthermore, in the fiber treatment agent of the present invention, unreacted components (A) and (B) may remain in addition to these condensates, provided that the turbidity is 1000 NTU or less.
[0026] (Component (A): Formaldehyde or its hydrate) Formaldehyde monohydrate (methanediol) is an example of a formaldehyde hydrate. Of these, formaldehyde is preferred from the viewpoint of providing high shape retention and durability to the natural fibers after treatment.
[0027] The content of the constituent element derived from component (A) in the fiber treatment agent of the present invention is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 1.5% by mass or more, even more preferably 3% by mass or more, and even more preferably 5% by mass or more, from the viewpoint of imparting high shape retention and strength to the natural fibers after treatment. Furthermore, in addition to the above viewpoint, from the viewpoint of formulation suitability, it is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less, even more preferably 35% by mass or less, and even more preferably 30% by mass or less. In other words, the content of the constituent element derived from component (A) in the fiber treatment agent of the present invention is preferably 0.1 to 60% by mass, more preferably 1 to 50% by mass, even more preferably 1.5 to 40% by mass, even more preferably 3 to 35% by mass, and even more preferably 5 to 30% by mass, from the viewpoint of imparting high shape retention and strength to the natural fibers after treatment and from the viewpoint of formulation suitability. In this specification, "components derived from component (A)" refers to the total content of the condensate that includes components derived from component (A) and the remaining component (A).
[0028] (Component (B): Triazine derivative represented by general formula (1)) The triazine derivative used in this invention is represented by the following general formula (1)
[0029] [ka]
[0030] [In the formula, R 1 ~R 3 These may be the same or different and represent a hydrogen atom, a hydroxymethylamino group, an amino group, a hydroxyl group, a halogen atom, a phenyl group, a linear or branched alkyl or alkenyl group having 1 to 6 carbon atoms, or a linear or branched alkoxy or alkenyloxy group having 1 to 6 carbon atoms.
[0031] Examples of triazine derivatives represented by general formula (1) include melamine, monomethylolmelamine, dimethylolmelamine, trimethylolmelamine, benzoguanamine, acetoguanamine, 2,4-diamino-1,3,5-triazine, ammeline, and 2-chloro-4,6-diamino-1,3,5-triazine. From the viewpoint of providing high shape retention and durability to the natural fibers after treatment, at least one selected from melamine, monomethylolmelamine, dimethylolmelamine, and trimethylolmelamine is preferred, with melamine being more preferred. Component (B) can be used alone or in combination of two or more types.
[0032] The content of the constituent element derived from component (B) in the fiber treatment agent of the present invention is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 2.5% by mass or more, and even more preferably 5% by mass or more, from the viewpoint of imparting high shape retention and strength to the natural fiber after treatment. Furthermore, in addition to the above viewpoint, from the viewpoint of improving the feel of the fiber surface, it is preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less, even more preferably 35% by mass or less, and even more preferably 30% by mass or less. In other words, the content of the component derived from component (B) in the fiber treatment agent of the present invention is preferably 0.1 to 60% by mass, more preferably 1 to 50% by mass, even more preferably 2.5 to 40% by mass, even more preferably 5 to 35% by mass, and even more preferably 5 to 30% by mass, from the viewpoint of imparting high shape retention and strength to the treated fibers and improving the feel of the fiber surface. In this specification, "components derived from component (B)" refers to the total content of the condensate that includes components derived from component (B) and the remaining component (B).
[0033] The total content of components derived from component (A) and components derived from component (B) in the fiber treatment agent of the present invention is, from the viewpoint of imparting high shape retention and strength to the natural fibers after treatment, more than 1% by mass, preferably 2.5% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more. Furthermore, from the viewpoint of improving the feel of the fiber surface, it is preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 60% by mass or less, even more preferably 50% by mass or less, and even more preferably 40% by mass or less.
[0034] The molar ratio (A) / (B) of components derived from component (A) to components derived from component (B) in the fiber treatment agent of the present invention is preferably 0.005 or more, more preferably 0.01 or more, even more preferably 0.05 or more, and even more preferably 0.1 or more, from the viewpoint of further improving the shape retention and strength of the natural fiber after treatment by forming condensates with larger molecular weights when water-soluble condensates condensate together within the natural fiber. Furthermore, from the viewpoint of a good feel, it is preferably less than 5, more preferably 4 or less, even more preferably 3 or less, and even more preferably 2 or less. In other words, the molar ratio (A) / (B) of components derived from component (A) to components derived from component (B) is preferably 0.005 or more and less than 5, more preferably 0.01 to 4, even more preferably 0.05 to 3, and even more preferably 0.1 to 2, from the viewpoint of further improving the shape retention and strength of the natural fiber after treatment due to the condensates formed by the condensation of water-soluble condensates within the natural fiber, and from the viewpoint of a good feel.
[0035] A condensate of component (A) and component (B) can be formed in a composition by heating a composition containing components (A) to (C). Initially, when the composition containing components (A) to (C) is prepared, components (A) and (B) exist in a free reaction with each other. However, by heating this composition, the two react to form a water-soluble condensate.
[0036] The content of the condensate formed from components (A) and (B) in the fiber treatment agent of the present invention is preferably more than 1% by mass, more preferably 1.5% by mass or more, even more preferably 2.5% by mass or more, even more preferably 5% by mass or more, and even more preferably 10% by mass or more, from the viewpoint of imparting high shape retention and strength to the natural fiber after treatment. In addition to the above viewpoint, from the viewpoint of improving the feel of the surface of the natural fiber, the content is preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 60% by mass or less, even more preferably 50% by mass or less, and even more preferably 40% by mass or less.
[0037] [Component (C): Water] The fiber treatment agent of the present invention uses water as a medium. The content of component (C) in the fiber treatment agent of the present invention is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, even more preferably 40% by mass or more, and also preferably 99% by mass or less, more preferably 97% by mass or less, even more preferably 95% by mass or less, and even more preferably 90% by mass or less. In other words, the content of component (C) in the fiber treatment agent of the present invention is preferably 10 to 99% by mass, more preferably 20 to 97% by mass, even more preferably 30 to 95% by mass, and even more preferably 40 to 90% by mass.
[0038] [Component (D): Hansen's solubility parameter SP value of 16-40 MPa] 1 / 2 [Organic compounds that are] When components (A) and (B) react, a large molecular weight insoluble condensate is formed in the fiber treatment agent of the present invention. This can lead to the formation of a hard resin layer on the surface of the natural fiber, restricting its movement such as bending and stretching, hindering its elasticity (toughness), and potentially worsening the feel of the fiber surface. Therefore, when treating natural fibers, the Hansen solubility parameter SP value should be 16 MPa, from the viewpoint of preventing aggregation of the condensate oligomers composed of components (A) and (B) that are generated during the reaction and cause increased turbidity, and facilitating their dissolution. 1 / 2 Above 40 MPa 1 / 2It is preferable to contain the following organic compounds (excluding organic salts and compounds having an aldehyde group with a molecular weight of 150 or less). Organic salts having a charge will cause a sharp increase in turbidity when coexisting in the system, and compounds having an aldehyde group such as glutaraldehyde will cause a sharp increase in turbidity by crosslinking triazine derivatives at multiple points, so they are excluded from component (D).
[0039] In the present invention, the SP value of Hansen solubility parameter refers to δTot (MPa 1 / 2 ) calculated at 25 °C in the DIY program using the software package HSPiP 4th Edition 4.1.07 based on Hansen Solubility Parameters: A User’s Handbook, CRC Press, Boca Raton FL, 2007.
[0040] Examples of the organic compound in which the SP value of the Hansen solubility parameter of component (D) is 16.0 MPa 1 / 2 or more and 40.0 MPa 1 / 2 or less include monohydric alcohols, dihydric alcohols, dihydric alcohol derivatives, polyhydric alcohols having three or more valences, lactams, imidazolidinones, pyrimidinones, lactones, alkylene carbonates, and other general-purpose organic solvents having an SP value within the above range.
[0041] The following are specific examples of compounds in which the SP value of the Hansen solubility parameter is 16.0 MPa 1 / 2 or more and 40.0 MPa 1 / 2 or less. The numerical values in parentheses in each example are the SP values calculated by the above-described method. · Examples of monohydric alcohols: ethanol (25.4), 1-propanol (22.9), isopropyl alcohol (22.3), 1-butanol (22.9) Examples of dihydric alcohols: Ethylene glycol (31.6), diethylene glycol (29.2), triethylene glycol (26.1), tetraethylene glycol (24.3), pentaethylene glycol (23.1), hexaethylene glycol (22.2), propylene glycol (31.7), 1-dipropylene glycol (26.0), tripropylene glycol (23.4) Examples of dihydric alcohol derivatives: Dipropylene glycol monomethyl ether (21.1), dipropylene glycol dimethyl ether (17.8), dipropylene glycol diacetate (19.0), dipropylene glycol monomethyl ether acetate (18.5) Examples of polyhydric alcohols with a valency of 35.7% or higher: Glycerin (35.7%), Sorbitol (35.8%) Examples of lactams: 2-pyrrolidone (24.8), N-methylpyrrolidone (22.0) Examples of imidazolidinones: Ethylene urea (28.5), 1,3-dimethyl-2-imidazolidinone (22.3), dihydroxymethylethyleneurea (31.3), N,N'-dihydroxymethyl-4,5-dihydroxyethyleneurea (34.7), DMDM hydantoin (28.1) • Example of pyrimidinone: N,N'-dimethylpropylene urea (21.3) • Example of a lactone: γ-butyrolactone (24.6) Examples of alkylene carbonates: ethylene carbonate (29.2), propylene carbonate (27.1) Examples of common organic solvents: DMF (N,N-dimethylformamide) (24.2), DMAc (N,N-dimethylacetamide) (23.0), DMSO (dimethyl sulfoxide) (23.6), THF (tetrahydrofuran) (18.2), 1,4-dioxane (20.5), acetonitrile (23.9)
[0042] From the viewpoint of preventing aggregation and facilitating dissolution of the condensate oligomer consisting of components (A) and (B), which are generated during the reaction process and cause an increase in turbidity, the SP value of Hansen's solubility parameter is set to 35.8 MPa. 1 / 2The following is preferable, and 34.7 MPa 1 / 2 The following is more preferable: 29.2 MPa 1 / 2 The following is even more preferable. From a similar viewpoint, 17.8 MPa 1 / 2 Preferably, the above, and 21.1 MPa. 1 / 2 More preferably, the above is true, and 22.0 MPa 1 / 2 It is even more preferable if the above conditions are met.
[0043] Among these, dihydric alcohols, lactams, and imidazolidinones are preferred, and at least one selected from diethylene glycol (29.2), triethylene glycol (26.1), N-methylpyrrolidone (22.0), 1,3-dimethyl-2-imidazolidinone (22.3), and DMDM hydantoin (28.1) is more preferred.
[0044] Component (D) can be used individually or in combination of two or more. The content of component (D) in the fiber treatment agent of the present invention is preferably 10% by mass or more, more preferably 15% by mass or more, and even more preferably 25% by mass or more, from the viewpoint of maintaining the turbidity of the fiber treatment agent at 1000 NTU or less for a longer period of time. Furthermore, from the viewpoint of efficiently promoting the condensation reaction and further improving the shape retention and strength of the treated natural fiber by forming a condensate with a larger molecular weight through the bonding of water-soluble condensates within the natural fiber, the content is preferably 80% by mass or less, more preferably 60% by mass or less, and even more preferably 45% by mass or less.
[0045] [Cationic surfactants] The fiber treatment agent of the present invention may contain a cationic surfactant to the extent that it does not impair the effects of the present invention. The cationic surfactant is preferably a monolong-chain alkylquaternary ammonium salt having one C8-C24 alkyl group and three C1-C4 alkyl groups.
[0046] Preferably, at least one monolong-chain alkylquaternary ammonium surfactant is selected from compounds represented by the following general formula.
[0047] [ka]
[0048] [In the formula, R 4 R is a saturated or unsaturated linear or branched alkyl group having 8 to 22 carbon atoms. 8 -CO-NH-(CH2) m - or R 8 -CO-O-(CH2) m -(R 8 (where m represents an integer from 1 to 4, and R represents a saturated or unsaturated linear or branched alkyl chain having 7 to 21 carbon atoms.) 5 , R 6 and R 7 These independently represent an alkyl group having 1 to 4 carbon atoms, or a hydroxylalkyl group having 1 to 4 carbon atoms, and X - This represents chloride ions, bromide ions, metosulfate ions, or ethosulfate ions.
[0049] Suitable cationic surfactants include, for example, long-chain quaternary ammonium compounds such as cetyltrimethylammonium chloride, myristyltrimethylammonium chloride, behentrimonium chloride, cetyltrimethylammonium bromide, and stearamidopropyltrimonium chloride, which can be used individually or as mixtures thereof.
[0050] The content of the cationic surfactant in the fiber treatment agent of the present invention is preferably 0.05% by mass or more, more preferably 0.10% by mass or more, and also preferably 10% by mass or less, more preferably 5% by mass or less, from the viewpoint of improving the feel of the natural fiber after treatment and further enhancing the effects of the present invention.
[0051] 〔silicone〕 Furthermore, the fiber treatment agent of the present invention may contain silicone to improve the feel and manageability of the natural fibers after treatment. Preferably, one or more silicones are selected from dimethylpolysiloxane and amino-modified silicones.
[0052] Any cyclic or acyclic dimethylpolysiloxane polymer can be used as the dimethylpolysiloxane, and examples include the SH200 series, BY22-019, BY22-020, BY11-026, B22-029, BY22-034, BY22-050A, BY22-055, BY22-060, BY22-083, FZ-4188 (all from Toray Dow Corning Co., Ltd.), KF-9088, KM-900 series, MK-15H, and MK-88 (all from Shin-Etsu Chemical Co., Ltd.).
[0053] Any silicone having an amino group or an ammonium group can be used as the amino-modified silicone. Examples include amino-modified silicone oil in which all or some of the terminal hydroxyl groups are terminally encapsulated with methyl groups, etc., and amodimethicone that is not terminally encapsulated. From the viewpoint of improving the feel and cohesiveness of the natural fibers after treatment, preferred amino-modified silicones include, for example, the compound shown in the following formula.
[0054] [ka]
[0055] [In the formula, R' is a hydrogen atom, a hydroxyl group or R X Show, R X represents a substituted or unsubstituted monovalent hydrocarbon group having 1 to 20 carbon atoms, and J is R X , R"-(NHCH2CH2) a NH2, OR XOr it represents a hydroxyl group, R'' represents a divalent hydrocarbon group having 1 to 8 carbon atoms, a represents a number from 0 to 3, and b and c represent a number such that their sum is number-average of 10 or more and less than 20,000, preferably 20 or more and less than 3,000, more preferably 30 or more and less than 1,000, and even more preferably 40 or more and less than 800.
[0056] Suitable commercially available amino-modified silicones include amino-modified silicone oils such as SF8452C and SS3551 (both from Toray Dow Corning Co., Ltd.), KF-8004, KF-867S, and KF-8015 (all from Shin-Etsu Chemical Co., Ltd.), and amodimethicone emulsions such as SM8704C, SM8904, BY22-079, FZ-4671, and FZ4672 (all from Toray Dow Corning Co., Ltd.).
[0057] The silicone content in the fiber treatment agent of the present invention is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, even more preferably 0.5% by mass or more, and also preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less, from the viewpoint of improving the feel of the natural fibers after treatment and further enhancing the effects of the present invention.
[0058] [Cationic polymers] Furthermore, the fiber treatment agent of the present invention may contain a cationic polymer from the viewpoint of improving the feel of the natural fiber after treatment.
[0059] Cationic polymers are polymers having a cationic group or a group that can be ionized into a cationic group, and also include amphoteric polymers that are cationic overall. Specifically, they are aqueous solutions containing an amino group or an ammonium group in the side chain of the polymer chain, or containing diallyl quaternary ammonium salt as a constituent unit, such as cationized cellulose derivatives, cationic starch, cationized guar gum derivatives, polymers or copolymers of diallyl quaternary ammonium salt, and quaternized polyvinylpyrrolidone derivatives. Of these, from the viewpoint of improving the softness, smoothness and ease of handling during rinsing and shampooing, ease of manageability and moisturizing properties during drying, and the stability of the agent, one or more selected from polymers containing diallyl quaternary ammonium salt as a constituent unit, quaternized polyvinylpyrrolidone derivatives, and cationized cellulose derivatives are preferred, and one or more selected from polymers or copolymers of diallyl quaternary ammonium salt and cationized cellulose derivatives are more preferred.
[0060] Specific examples of suitable polymers or copolymers of diallyl quaternary ammonium salts include dimethyldiallylammonium chloride polymer (Polyquaternium-6, e.g., Merquart 100; Lubrizol Advanced Materials), dimethyldiallylammonium chloride / acrylic acid copolymer (Polyquaternium-22, e.g., Merquart 280, 295; Lubrizol Advanced Materials), and dimethyldiallylammonium chloride / acrylamide copolymer (Polyquaternium-7, e.g., Merquart 550; Lubrizol Advanced Materials).
[0061] Specific examples of suitable quaternized polyvinylpyrrolidone derivatives include polymers obtained by polymerizing vinylpyrrolidone copolymer and dimethylaminoethyl methacrylate (polyquaternium-11, e.g., Gaffcut 734, Gaffcut 755, Gaffcut 755N (all from Ashland)).
[0062] Suitable examples of cationized cellulose include polymers obtained by loading hydroxycellulose with glycidyltrimethylammonium chloride (Polyquaternium-10, e.g., Leoguard G, GP (both from Lion Corporation), Polymer JR-125, JR-400, JR-30M, LR-400, LR-30M (all from Amarcol)), and hydroxyethylcellulose dimethyldiallylammonium chloride (Polyquaternium-4, e.g., Cellcoat H-100, L-200 (both from AkzoNobel)).
[0063] The content of the cationic polymer in the fiber treatment agent of the present invention is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.05% by mass or more, and also preferably 20% by mass or less, more preferably 10% by mass or less, from the viewpoint of improving the feel of the natural fiber after treatment.
[0064] Furthermore, the fiber treatment agent of the present invention may contain antioxidants such as ascorbic acid; and pH adjusters such as sodium hydroxide, potassium hydroxide, phosphoric acid, hydrochloric acid, and tartaric acid.
[0065] [Turbidity] The fiber treatment agent of the present invention is desirable to have as low turbidity as possible from the viewpoint of improving the elasticity (toughness) of naturally derived fibers and improving the feel of the fiber surface. The turbidity of the fiber treatment agent is 1000 NTU or less, preferably 500 NTU or less, more preferably 100 NTU or less, and even more preferably 20 NTU or less. The above turbidity of the fiber treatment agent refers to the turbidity caused by component (B) and water-insoluble condensates formed by the bonding of water-soluble condensates. If other components that cause turbidity are included, only the turbidity caused by component (B) and water-insoluble condensates shall be considered. In this case, the quantitative determination of water-insoluble condensates can be performed, for example, by filtration with a membrane filter with a pore size of 0.1 μm followed by derivatization pyrolysis GC / MS.
[0066] Here, NTU (Nephelometric Turbidity Unit) is a turbidity unit in the turbidimetry method using formazin as the turbidity standard solution. The turbidity of the fiber treatment agent can be measured at room temperature (25°C) by placing the fiber treatment agent directly into the measurement cell of a digital turbidimeter (AS ONE Corporation / model number: TB700).
[0067] [Issue] The pH of the fiber treatment agent of the present invention is preferably 3.0 or higher, more preferably 3.5 or higher, even more preferably 4.0 or higher, and still more preferably 4.5 or higher, and also preferably 12.0 or lower, more preferably 11.0 or lower, even more preferably 10.0 or lower, and still more preferably 9.0 or lower, from the viewpoint of suppressing damage to natural fibers. Note that the pH values in the present invention are those at 25°C. In other words, the pH of the fiber treatment agent of the present invention is preferably 3.0 to 12.0, more preferably 3.5 to 11.0, even more preferably 4.0 to 10.0, and even more preferably 4.5 to 9.0, from the viewpoint of suppressing damage to natural fibers.
[0068] [Method for manufacturing fiber treatment agent] The fiber treatment agent of the present invention can be produced by heating a composition containing components (A) to (C), wherein the total amount of components derived from component (A) and components derived from component (B) exceeds 1% by mass, until the turbidity becomes 1000 NTU or less. Initially, when the composition containing components (A) to (C) is prepared, components (A) and (B) exist in a free reaction with each other, resulting in high turbidity. However, by heating this composition, the two react to form a water-soluble condensate, which reduces the turbidity of the composition. The fiber treatment agent of the present invention is obtained from this composition, where the turbidity has become 1000 NTU or less.
[0069] The heating temperature required to reduce the turbidity of a composition containing components (A) to (C) to 1000 NTU or less is preferably 85°C or higher, more preferably 88°C or higher, and even more preferably 90°C or higher, from the viewpoint of efficiently promoting the reaction in which components (A) and (B) in the fiber treatment agent react to form a water-soluble condensate. Furthermore, from the viewpoint of preventing the reaction from becoming too fast and uncontrollable, the heating temperature is preferably 120°C or lower, more preferably 115°C or lower, and even more preferably 110°C or lower.
[0070] Furthermore, the heating time is preferably 1 minute or more, more preferably 5 minutes or more, preferably 20 minutes or less, and more preferably 15 minutes or less. It is desirable to raise the temperature to the above temperature in a short time, and after confirming transparency by heating and stirring, to cool it down in a short time to the fiber application temperature or the storage temperature of the fiber treatment agent described later. If rapid temperature increase is difficult due to scale-up, it is advantageous to raise the temperature with the composition other than component (B) mixed in, and then add component (B) when the above temperature is reached.
[0071] The pH of the composition containing components (A) to (C) when heated is preferably 7.0 or higher, more preferably 8.0 or higher, and even more preferably 9.0 or higher, from the viewpoint of preventing the reaction from proceeding too quickly and entering Phase 3. Furthermore, from the viewpoint of ease of workability in order to facilitate pH adjustment when applying to fibers, the pH is preferably 13.0 or lower, more preferably 12.0 or lower, and even more preferably 11.0 or lower. After the turbidity of the composition becomes 1000 NTU or less, it can be adjusted to the preferred pH range of the aforementioned fiber treatment agent as needed.
[0072] [Storage method for fiber treatment agents] When transporting and storing the treatment agent with a turbidity of 1000 NTU or less, manufactured as described above, before application to fibers, the storage temperature can be kept low to prevent unintended reaction progression during transport. From the viewpoint of preventing freezing and recrystallization, the storage temperature is preferably 1°C or higher, more preferably 2°C or higher, and even more preferably 5°C or higher. From the viewpoint of preventing unintended reaction progression, it is preferably 25°C or lower, more preferably 20°C or lower, and even more preferably 15°C or lower. Furthermore, the pH of the fiber treatment agent during storage is preferably adjusted to a range of 9 to 11, which indicates a slow condensation rate.
[0073] [Fiber processing method] (Basic procedures) By treating natural fibers using the fiber treatment agent of the present invention in a method including the following step (i), it is possible to impart shape retention and high durability to natural fibers while maintaining their elasticity (toughness) to a high degree. (i) A step of immersing natural fibers in the fiber treatment agent of the present invention and treating them while maintaining a state in which the turbidity of the treatment agent is 1000 NTU or less.
[0074] Furthermore, the fiber treatment agent of the present invention, which has a turbidity of 1000 NTU or less and is manufactured as described above, may be applied to the fibers as is. However, the elasticity of the fibers can be further enhanced by heating the treatment agent for a certain period of time before applying it to the fibers, to the extent that it does not cause an increase in turbidity due to the treatment agent entering Phase 3. For this reason, it is preferable to include the following step (0) before step (i). (0) A step of heating the fiber treatment agent.
[0075] From the viewpoint of improving productivity, the heating temperature in step (0) is preferably 40°C or higher, more preferably 60°C or higher, and even more preferably 70°C or higher. Furthermore, from the viewpoint of being able to stop heating at an appropriate point, it is preferably 120°C or lower, more preferably 105°C or lower, and even more preferably 99°C or lower.
[0076] The heating time in step (0) is defined as the heating time from when the prepared treatment agent, which has a turbidity of 1000 NTU or less, is heated until the treatment agent reaches phase 3 and its turbidity exceeds 1000 NTU again, with T being the heating time. From the viewpoint of exhibiting the stretchability effect on the fibers, the heating time is preferably 0.2T or more, more preferably 0.3T or more, and even more preferably 0.4T or more. Furthermore, from the viewpoint of ensuring the time until the turbidity exceeds 1000 NTU when it reaches phase 3, i.e., the time during which the fibers can be processed, the heating time is preferably 0.8T or less, more preferably 0.7T or less, and even more preferably 0.6T or less.
[0077] In step (i), the natural fibers to be immersed in the fiber treatment agent may be dry or wet. The amount of fiber treatment agent used to immerse the natural fibers is preferably 2 or more, more preferably 3 or more, even more preferably 5 or more, even more preferably 10 or more, even more preferably 20 or more, and also preferably 500 or less, more preferably 250 or less, and even more preferably 100 or less, in terms of the bath ratio to the mass of the natural fibers (mass of fiber treatment agent / mass of natural fibers). In other words, the bath ratio is preferably 2 to 500, more preferably 3 to 250, even more preferably 5 to 100, even more preferably 10 to 100, and even more preferably 20 to 100.
[0078] Furthermore, in step (i), the natural fibers may be fixed in advance with a curler or the like, and then immersed in the fiber treatment agent of the present invention under heating. In this way, the natural fibers can be given shape retention and high durability, as well as the desired shape, simultaneously.
[0079] In step (i), the immersion of the natural fiber into the fiber treatment agent is carried out under heating, which is done by warming the fiber treatment agent. This heating may be done by immersing the natural fiber into the heated fiber treatment agent, or by immersing the natural fiber into the low-temperature fiber treatment agent and then heating it. The temperature of the fiber treatment agent is preferably 20°C or higher, more preferably 35°C or higher, and even more preferably 45°C or higher, in order to obtain the effects of the present invention by increasing the interaction between the water-soluble condensate formed from component (A) and component (B) and the fiber constituent molecules in the natural fiber, such as protein molecules, and by promoting the condensation and growth reaction between the condensates made of component (A) and component (B) within the natural fiber. Furthermore, in order to prevent the natural fiber from denatured and degraded by heat, the temperature is preferably less than 100°C, more preferably 80°C or lower, even more preferably 70°C or lower, and even more preferably 60°C or lower.
[0080] In step (i), the immersion time is preferably 0.3T or more, more preferably 0.4T or more, and even more preferably 0.5T or more, from the viewpoint of exhibiting an effect of improving the elasticity of natural fibers, when T is defined as the heating time of the treatment agent, which has a turbidity of 1000 NTU or less immediately after preparation, until the turbidity of the treatment agent exceeds 1000 NTU, and in order to suppress damage to natural fibers, it is preferably 0.95T or less, more preferably 0.90T or less, and even more preferably 0.85T or less.
[0081] The specific immersion time is adjusted as appropriate depending on the heating temperature used, but for example, from the viewpoint of exhibiting an effect of improving the elasticity of natural fibers, it is preferably 15 minutes or more, more preferably 30 minutes or more, and even more preferably 1 hour or more. Furthermore, in order to suppress damage to natural fibers, it is preferably 48 hours or less, more preferably 24 hours or less, and even more preferably 12 hours or less.
[0082] Step (i) is preferably carried out in an environment in which the evaporation of moisture is suppressed. Specific means of suppressing the evaporation of moisture include covering the container of the fiber treatment agent in which the natural fibers are immersed with a film-like substance, cap, lid, etc., made of a material that does not allow water vapor to pass through.
[0083] After step (i), the natural fibers may be rinsed or not, but rinsing is preferable from the viewpoint of preventing a deterioration in the feel of the natural fibers due to excess polymers.
[0084] These processes are thought to cause water-soluble condensates generated from components (A) and (B) to penetrate into the natural fibers, leading to interactions with the fiber constituent molecules within the natural fibers, such as protein molecules. Furthermore, these water-soluble condensates condensate together within the natural fibers to form condensates with larger molecular weights. Since these condensates remain within the natural fibers even after washing, the shape of the natural fibers treated by the method of the present invention does not collapse even after washing.
[0085] If the turbidity of the treatment agent increases during step (i), a hard resin layer will form on the surface of the natural fiber, making it difficult to maintain the elasticity (toughness) of the natural fiber and to ensure a good feel on the fiber surface. Therefore, it is preferable to remove the natural fiber from the treatment agent before the turbidity of the treatment agent exceeds 1000 NTU. The turbidity of the treatment agent can be checked by taking a sample from the treatment agent as appropriate and using the turbidity measurement method described above. If the natural fiber removed during treatment is not sufficiently treated, step (i) can be repeated. That is, it is preferable to include the following step (ii) after step (i) and repeat steps (i) and (ii) two or more times. (ii) The process of removing the natural fibers from the treatment agent before the turbidity of the treatment agent exceeds 1000 NTU.
[0086] After removing the natural fibers from the treatment agent in step (ii) above, it is preferable to rinse the surface of the natural fibers to wash away the insoluble condensate. In other words, it is preferable to perform step (iii) below after step (ii). (iii) The process of rinsing the extracted natural fibers.
[0087] The rinsing in step (iii) is preferably carried out using a composition containing the aforementioned component (D). This rinsing composition may consist only of component (D), or it may also contain water in addition to component (D). When water is included, the content of component (D) in the rinsing composition is preferably 60% by mass or more, more preferably 80% by mass or more, and even more preferably 95% by mass or more.
[0088] (Post-crosslinking treatment) After steps (i) to (iii), step (iv) below may be performed to further improve the shape retention of the natural fibers. (iv) A step of immersing natural fibers in a post-crosslinking agent containing components (E) and (C). (E): At least one formaldehyde derivative selected from formaldehyde, formaldehyde hydrate, glyoxylic acid, glyoxylic acid hydrate, glyoxylate, glyoxal, glyoxal hydrate, glutaraldehyde, and glutaraldehyde hydrate. (C):Water
[0089] The content of component (E) in the post-crosslinking agent is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 1% by mass or more, and also preferably 60% by mass or less, more preferably 40% by mass or more, and even more preferably 20% by mass or less. In other words, the content of component (E) in the post-crosslinking agent is preferably 0.01 to 60% by mass, more preferably 0.1 to 40% by mass, and even more preferably 1 to 20% by mass.
[0090] Furthermore, the post-crosslinking agent may contain pH adjusters such as sodium hydroxide, potassium hydroxide, phosphoric acid, hydrochloric acid, and organic acids. On the other hand, from the viewpoint of improving the surface feel of naturally derived fibers, it is preferable that the post-crosslinking agent does not contain the triazine derivative of component (B).
[0091] From the viewpoint of suppressing damage to natural fibers, the pH of the post-crosslinking agent is preferably 11.0 or less, more preferably 10.0 or less, even more preferably 9.0 or less, and also preferably 2.0 or higher, more preferably 3.0 or higher, and even more preferably 4.0 or higher. In other words, the pH of the post-crosslinking agent is preferably 2.0 to 11.0, more preferably 3.0 to 10.0, and even more preferably 4.0 to 9.0, from the viewpoint of suppressing damage to natural fibers.
[0092] The temperature of the post-crosslinking agent used in step (iv) is preferably 20°C or higher, more preferably 35°C or higher, and even more preferably 45°C or higher, from the viewpoint of increasing the interaction between the condensate of component (A) and component (B) formed in the natural fiber and the fiber constituent molecules in the natural fiber, such as protein molecules, and enhancing the effects of the present invention (shape retention and strength). Furthermore, from the viewpoint of preventing the natural fiber from denatured and degraded by heat, the temperature is preferably less than 100°C, more preferably 80°C or lower, even more preferably 70°C or lower, and even more preferably 60°C or lower.
[0093] In step (iv), the natural fibers to be immersed in the post-crosslinking agent may be dry or wet. The amount of post-crosslinking agent used to immerse the natural fibers is preferably 2 or more, more preferably 3 or more, even more preferably 5 or more, even more preferably 10 or more, even more preferably 20 or more, and also preferably 500 or less, more preferably 250 or less, and even more preferably 100 or less, in terms of the bath ratio to the mass of the natural fibers (mass of post-crosslinking agent / mass of fibers treated in steps (i) to (iii)). In other words, the bath ratio is preferably 2 to 500, more preferably 3 to 250, even more preferably 5 to 100, even more preferably 10 to 100, and even more preferably 20 to 100.
[0094] In step (iv), the immersion time of the natural fibers in the post-crosslinking agent is preferably 1 minute or more, more preferably 3 minutes or more, even more preferably 5 minutes or more, and also preferably 5 hours or less, more preferably 3 hours or less, and even more preferably 1 hour or less, in order to allow the post-crosslinking agent to penetrate and diffuse into the natural fibers.
[0095] [Further processing may be added] In addition to the steps (i) to (iv) described above, the fiber processing method of the present invention may further include one or more additional treatments selected from decolorization, dyeing, surface finishing for imparting hydrophobicity and reducing friction, and heat treatment for further improving fiber elasticity (toughness).
[0096] In this case, the decolorization and dyeing processes may be performed before or after steps (i) to (iv) described above, or between each of steps (i) to (iv). Furthermore, multiple processes can be combined and added, and if both decolorization and dyeing are added, the order of the processes does not matter, except that decolorization must be performed before dyeing, and another process can be performed between decolorization and dyeing.
[0097] On the other hand, surface finishing for hydrophobicity and friction reduction, and heat treatment for further improvement of fiber elasticity (toughness) must be performed after steps (i) to (iii) above, or after step (iv) if treatment with a crosslinking agent is also performed after step (iv). In particular, better results can be obtained by performing these additional steps after step (iv). Furthermore, if surface finishing for hydrophobicity and friction reduction, and heat treatment for further improvement of fiber elasticity (toughness) are performed at a later stage than steps (i) to (iii) or step (iv) as described above, the order of treatment with decolorization and dyeing is not particularly limited.
[0098] (bleaching) Decolorization is carried out by immersing natural fibers in a decolorizing agent composition containing an alkaline agent, an oxidizing agent, and water. The decolorizing agent composition is usually in two parts: the first part contains an alkaline agent and water, and the second part contains an oxidizing agent and water. These two parts are typically stored separately and mixed before immersing the natural fibers.
[0099] Suitable alkaline agents include, but are not limited to, ammonia and its salts; alkanolamines (monoethanolamine, isopropanolamine, 2-amino-2-methylpropanol, 2-aminobutanol, etc.) and their salts; alkanediamines (1,3-propanediamine, etc.) and their salts; and carbonates (guanidine carbonate, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, etc.) and mixtures thereof.
[0100] The alkaline agent content in the decolorizing agent composition (in the case of a two-part type, a mixture of the first and second components) is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, and also preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 7.5% by mass or less.
[0101] Suitable oxidizing agents include, but are not limited to, hydrogen peroxide, urea peroxide, melamine peroxide, and sodium bromate. Among these oxidizing agents, hydrogen peroxide is preferred.
[0102] The content of the oxidizing agent in the decolorizing agent composition is preferably 1% by mass or more, more preferably 2% by mass or more, and also preferably 15% by mass or less, more preferably 12% by mass or less, and even more preferably 9% by mass or less.
[0103] When the first and second agents are stored separately, the pH of the second agent at 25°C is preferably 2 or higher, more preferably 2.5 or higher, and also preferably 6 or lower, more preferably 4 or lower. This pH can be adjusted with a suitable buffer. The pH of the decolorizing agent composition at 25°C is preferably 6 or higher, more preferably 6.5 or higher, even more preferably 6.8 or higher, and also preferably 11 or lower, more preferably 10.5 or lower, and even more preferably 10 or lower.
[0104] (staining) Dyeing is carried out by immersing natural fibers in a dyeing composition. The dyeing composition contains dyes and may optionally contain alkaline agents, acids, oxidizing agents, etc. Examples of dyes include direct dyes, oxidation dyes, and combinations thereof.
[0105] The type of direct dye is not particularly limited, and any direct dye suitable for dyeing can be used. Examples of direct dyes include anionic dyes, nitro dyes, disperse dyes, cationic dyes, and dyes having an azophenol structure selected from the group consisting of HC Red 18, HC Blue 18, and HC Yellow 16, as well as salts thereof and mixtures thereof.
[0106] [ka]
[0107] Examples of cationic dyes include, but are not limited to, Basic Blue 6, Basic Blue 7, Basic Blue 9, Basic Blue 26, Basic Blue 41, Basic Blue 99, Basic Brown 4, Basic Brown 16, Basic Brown 17, Natural Brown 7, Basic Green 1, Basic Orange 31, Basic Red 2, Basic Red 12, Basic Red 22, Basic Red 51, Basic Red 76, Basic Violet 1, Basic Violet 2, Basic Violet 3, Basic Violet 10, Basic Violet 14, Basic Yellow 57, and Basic Yellow 87, as well as mixtures thereof. Basic Red 51, Basic Orange 31, Basic Yellow 87, and mixtures thereof are particularly preferred.
[0108] Examples of anionic dyes include Acid Black 1, Acid Blue 1, Acid Blue 3, Acid Blue 5, Acid Blue 7, Acid Blue 9, Acid Blue 74, Acid Orange 3, Acid Orange 4, Acid Orange 6, Acid Orange 7, Acid Orange 10, Acid Red 1, Acid Red 14, Acid Red 18, Acid Red 27, Acid Red 33, Acid Red 50, Acid Red 52, Acid Red 73, Acid Red 87, Acid Red 88, Acid Red 92, Acid Red 155, Acid Red 180, Acid Violet 2, Acid Violet 9, Acid Violet 43, Acid Violet 49, Acid Yellow 1, Acid Examples include, but are not limited to, Yellow 10, Acid Yellow 23, Acid Yellow 3, Food Yellow No. 8, D&C Brown No. 1, D&C Green No. 5, D&C Green No. 8, D&C Orange No. 4, D&C Orange No. 10, D&C Orange No. 11, D&C Red No. 21, D&C Red No. 27, D&C Red No. 33, D&C Violet 2, D&C Yellow No. 7, D&C Yellow No. 8, D&C Yellow No. 10, FD&C Red 2, FD&C Red 40, FD&C Red No. 4, FD&C Yellow No. 6, FD&C Blue 1, Food Black 1, Food Black 2, as well as alkali metal salts of these (sodium salts, potassium salts, etc.) and mixtures thereof.
[0109] Among these, preferred anionic dyes are Acid Black 1, Acid Red 52, Acid Violet 2, Acid Violet 43, Acid Red 33, Acid Orange 4, Acid Orange 7, Acid Red 27, Acid Yellow 3, and Acid Yellow 10, as well as their salts. More preferred anionic dyes are Acid Red 52, Acid Violet 2, Acid Red 33, Acid Orange 4, and Acid Yellow 10, as well as their salts and mixtures.
[0110] Examples of nitro dyes include HC Blue No. 2, HC Blue No. 4, HC Blue No. 5, HC Blue No. 6, HC Blue No. 7, HC Blue No. 8, HC Blue No. 9, HC Blue No. 10, HC Blue No. 11, HC Blue No. 12, HC Blue No. 13, HC Brown No. 1, HC Brown No. 2, HC Green No. 1, HC Orange No. 1, HC Orange No. 2, HC Orange No. 3, HC Orange No. 5, HC Red BN, HC Red No. 1, HC Red No. 3, HC Red No. 7, HC Red No. 8, HC Red No. 9, HC Red No. 10, HC Red No. 11, HC Red No. 13, HC Red No. 54, HC Red No. 14, HC Violet BS, HC Examples include, but are not limited to, Violet No. 1, HC Violet No. 2, HC Yellow No. 2, HC Yellow No. 4, HC Yellow No. 5, HC Yellow No. 6, HC Yellow No. 7, HC Yellow No. 8, HC Yellow No. 9, HC Yellow No. 10, HC Yellow No. 11, HC Yellow No. 12, HC Yellow No. 13, HC Yellow No. 14, HC Yellow No. 15, 2-amino-6-chloro-4-nitrophenol, picramic acid, 1,2-diamino-4-nitrobenzol, 1,4-diamino-2-nitrobenzol, 3-nitro-4-aminophenol, 1-hydroxy-2-amino-3-nitrobenzol, and 2-hydroxyethylpicramic acid, as well as mixtures thereof.
[0111] Examples of disperse dyes include, but are not limited to, Disperse Blue 1, Disperse Black 9, and Disperse Violet 1, and mixtures thereof.
[0112] These direct dyes can be used individually or in combination of two or more, and direct dyes with different ionic properties can also be used together.
[0113] From the viewpoint of obtaining sufficient dyeing properties, the content of direct dyes in the dyeing agent composition is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, and even more preferably 0.05% by mass or more. From the viewpoint of compatibility, it is preferably 10% by mass or less, more preferably 7.5% by mass or less, even more preferably 5.0% by mass or less, and even more preferably 3.0% by mass or less.
[0114] If the dyeing composition contains only direct dyes as dyes, an oxidizing agent is not necessary to dye natural fibers. However, if you want to lighten the color of natural fibers, you can include an oxidizing agent in the composition.
[0115] When a dyeing composition contains an oxidative dye, it is usually a two-part system. The first part contains an oxidative dye intermediate (precursor and coupler) and an alkaline agent, while the second part contains an oxidizing agent such as hydrogen peroxide. These two parts are usually stored separately and mixed before immersing the natural fiber.
[0116] There are no particular restrictions on the oxidation dye intermediate; any known precursor and coupler commonly used in dyed products can be suitably used.
[0117] Precursors include, for example, paraphenylenediamine, toluene-2,5-diamine, 2-chloro-paraphenylenediamine, N-methoxyethyl-paraphenylenediamine, N-phenylparaphenylenediamine, N,N-bis(2-hydroxyethyl)-paraphenylenediamine, 2-(2-hydroxyethyl)-paraphenylenediamine, 2,6-dimethyl-paraphenylenediamine, 4,4'-diaminodiphenylamine, 1,3-bis(N-(2-hydroxyethyl)-N-(4-aminophenyl)amino)-2-propanol, PEG-3,3,2'-paraphenylenediamine, para-aminophenol, para-methylaminophenol, 3 Examples include, but are not limited to, methyl-4-aminophenol, 2-aminomethyl-4-aminophenol, 2-(2-hydroxyethylaminomethyl)-4-aminophenol, orthoaminophenol, 2-amino-5-methylphenol, 2-amino-6-methylphenol, 2-amino-5-acetamidophenol, 3,4-diaminobenzoic acid, 5-aminosalicylic acid, 2,4,5,6-tetraaminopyrimidine, 2,5,6-triamino-4-hydroxypyrimidine, 4,5-diamino-1-(4'-chlorobenzyl)pyrazole, 4,5-diamino-1-hydroxyethylpyrazole, and salts of these substances and mixtures thereof.
[0118] Examples of couplers include metaphenylenediamine, 2,4-diaminophenoxyethanol, 2-amino-4-(2-hydroxyethylamino)anisole, 2,4-diamino-5-methylphenethole, 2,4-diamino-5-(2-hydroxyethoxy)toluene, 2,4-dimethoxy-1,3-diaminobenzene, 2,6-bis(2-hydroxyethylamino)toluene, 2,4-diamino-5-fluorotoluene, 1,3-bis(2,4-diaminophenoxy)propane, metaaminophenol, 2-methyl-5-aminophenol, 2-methyl-5-(2-hydroxyethylamino)phenol, 2,4-dichloro-3-aminophenol, 2-chloro-3-amino-6-methylphenol, 2-methyl-4-chloro-5-aminophenol, N-cyclopentyl-methaminophenol, 2-methyl-4-methoxy-5-(2-hydroxyethylamino)phenol, 2-methyl-4-fluoro-5-aminophenol, para-amino-o-toxylethanolamine Zol, resorcinol, 2-methylresorcinol, 4-chlororesorcinol, 1-naphthol, 1,5-dihydroxynaphthalene, 1,7-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 2-isopropyl-5-methylphenol, 4-hydroxyindole, 5-hydroxyindole, 6-hydroxyindole, 7-hydroxyindole, 6-hydroxybenzomorpholine, 3,4-methylenedioxyphenol, 2-bromo-4,5-methylenedioxyphenol Examples include, but are not limited to, 3,4-methylenedioxyaniline, 1-(2-hydroxyethyl)amino-3,4-methylenedioxybenzene, 2,6-dihydroxy-3,4-dimethylpyridine, 2,6-dimethoxy-3,5-diaminopyridine, 2,3-diamino-6-methoxypyridine, 2-methylamino-3-amino-6-methoxypyridine, 2-amino-3-hydroxypyridine, 2,6-diaminopyridine, and salts of these substances and mixtures thereof.
[0119] The content of precursor and coupler in the dyeing agent composition is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and preferably 10% by mass or less, more preferably 7.5% by mass or less, and even more preferably 5% by mass or less.
[0120] If the dyeing composition contains an oxidation dye, it further contains an alkaline agent. Suitable alkaline agents include, but are not limited to, ammonia and its salts; alkanolamines (monoethanolamine, isopropanolamine, 2-amino-2-methylpropanol, 2-aminobutanol, etc.) and their salts; alkanediamines (1,3-propanediamine, etc.) and their salts; and carbonates (guanidine carbonate, sodium carbonate, potassium carbonate, sodium bicarbonate, potassium bicarbonate, etc.); and mixtures thereof.
[0121] The content of the alkaline agent in the dyeing agent composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, and also preferably 15% by mass or less, more preferably 10% by mass or less, and even more preferably 7.5% by mass or less.
[0122] When the dyeing composition contains an oxidative dye, the oxidizing agent composition (second agent) is stored separately from the oxidative dye composition (first agent) and mixed before immersing the natural fiber. Suitable oxidizing agents include, but are not limited to, hydrogen peroxide, urea peroxide, melamine peroxide, and sodium bromate. Among these oxidizing agents, hydrogen peroxide is preferred.
[0123] The content of the oxidizing agent in the dyeing agent composition is preferably 1% by mass or more, more preferably 2% by mass or more, and also preferably 15% by mass or less, more preferably 12% by mass or less, and even more preferably 9% by mass or less.
[0124] When the first and second agents are stored separately, the pH of the second agent at 25°C is preferably 2 or higher, more preferably 2.5 or higher, and also preferably 6 or lower, more preferably 4 or lower. This pH can be adjusted with a suitable buffer. The pH of the dyeing composition obtained by mixing the first and second agents at 25°C is preferably 6 or higher, more preferably 6.5 or higher, even more preferably 6.8 or higher, and also preferably 11 or lower, more preferably 10.5 or lower, and even more preferably 10 or lower.
[0125] If the dyeing composition contains an oxidation dye, it may further contain the direct dyes exemplified above.
[0126] The dyeing composition may preferably further contain the following surfactants, conditioning components, etc., and may preferably take the form of a solution, emulsion, cream, paste, or mousse.
[0127] The temperature of the dyeing agent composition is preferably 0°C or higher, more preferably 10°C or higher, even more preferably 20°C or higher, and also preferably 90°C or lower, more preferably 80°C or lower, from the viewpoint of efficiently penetrating and diffusing the dyeing agent composition into the natural fiber and further enhancing the dyeing effect.
[0128] (Surface finish for imparting hydrophobicity and reducing friction) Surface finishing for hydrophobicity and friction reduction is performed by immersing the natural fibers in the surface finishing agent shown below, in a stage after steps (i) to (iii) described above, or in a stage after step (iv) if a crosslinking agent is used after step (iv).
[0129] The surface finishing agent contains the following components (F) and (C). (F) Epoxyaminosilane copolymer, which is the reaction product of the following compounds (a) to (d) (a) Polysiloxane having at least two oxyranyl groups or oxetanyl groups (b) Polyether having at least two oxyranyl or oxetanyl groups (c) Aminopropyltrialkoxysilane (d) Compounds selected from the group consisting of the following primary and secondary amines Primary amines: Methylamine, ethylamine, propyleneamine, ethanolamine, isopropylamine, butylamine, isobutylamine, hexylamine, dodecylamine, oleylamine, aniline, aminopropyltrimethylsilane, aminopropyltriethylsilane, aminomorpholine, aminopropyldiethylamine, benzylamine, naphthylamine, 3-amino-9-ethylcarbazole, 1-aminoheptafluorohexane, 2,2,3,3,4,4,5,5,6,6,7,7,8,8,8-pentadecafluoro-1-octaneamine Secondary amines: Methylethylamine, methyloctadecylamine, diethanolamine, dibenzylamine, dihexylamine, dicyclohexylamine, piperidine, pyrrolidinephthalimide, polymeramines (C) Water
[0130] [Ingredient (F): Epoxyaminosilane copolymer] The epoxyaminosilane copolymer of component (F) is the reaction product of the compounds (a) to (d) shown below.
[0131] <Compounds (a), (b)> Compound (a) is a polysiloxane containing at least two oxiranyl groups or oxetanyl groups, for example, one represented by the following general formula (5).
[0132] [ka]
[0133] [In the formula, R represents a C1-C6 hydrocarbon group that may contain heteroatoms and has an oxyranyl or oxetanyl group at its terminus, and x represents a number from 1 to 1000.]
[0134] Compound (b) is a polyether containing at least two oxyranyl groups or oxetanyl groups, for example, one represented by the following general formula (6).
[0135] [ka]
[0136] [In the formula, R has the same meaning as above, y is between 1 and 100, z is between 0 and 100, and y+z is between 1 and 200.]
[0137] In general formulas (5) and (6), an oxygen atom is preferred as the heteroatom that R may contain. Examples of R include oxyranylmethyl group (glycidyl group), oxyranylmethoxy group (glycidyloxy group), oxyranylmethoxypropyl group (glycidyloxypropyl group), oxetanylmethyl group, oxetanylmethoxy group, oxetanylmethoxypropyl group, 3-ethyloxetanylmethyl group, etc., and among these, a hydrocarbon group having 1 to 4 carbon atoms that has an oxyranyl group and may contain a heterooxygen atom is preferred, and at least one selected from oxyranylmethyl group (glycidyl group), oxyranylmethoxy group (glycidyloxy group), and oxyranylmethoxypropyl group (glycidyloxypropyl group) is even more preferred.
[0138] <Compound (c)> Compound (c) is aminopropyltrialkoxysilane. The alkoxy group in compound (c) may have 1 to 6 carbon atoms, preferably 2 to 4 carbon atoms, and more preferably 3 carbon atoms, with isopropoxy being particularly preferred. Examples of compound (c) include aminopropyltrimethoxysilane, aminopropyltriethoxysilane, aminopropyltripropoxysilane, aminopropyltriisopropoxysilane, aminopropyltributoxysilane, and aminopropyltritert-butoxysilane, with aminopropyltriisopropoxysilane being particularly preferred. Compound (c) can be used individually or in combination of two or more.
[0139] <Compound (d)> Compound (d) is a compound selected from the group consisting of the following primary and secondary amines. Primary amines: Methylamine, ethylamine, propyleneamine, ethanolamine, isopropylamine, butylamine, isobutylamine, hexylamine, dodecylamine, oleylamine, aniline, aminopropyltrimethylsilane, aminopropyltriethylsilane, aminomorpholine, aminoethyldimethylamine, aminoethyldiethylamine, aminoethyldibutylamine, aminopropyldimethylamine, aminopropyldiethylamine, aminopropyldibutylamine, benzylamine, naphthylamine, 3-amino-9-ethylcarbazole, 1-aminoheptafluorohexane, 2,2,3,3,4,4,5,5,6,6,7,7,8,8,8-pentadecafluoro-1-octaneamine Secondary amines: Methylethylamine, methyloctadecylamine, diethanolamine, dibenzylamine, dihexylamine, dicyclohexylamine, piperidine, pyrrolidinephthalimide, polymeramines
[0140] Of these, primary amines are preferred, and one selected from aminopropyldiethylamine, aminopropyldimethylamine, and aminopropyldibutylamine is even more preferred. Compound (d) can be used individually or in combination of two or more.
[0141] The reaction of compounds (a) to (d) is carried out, for example, by refluxing in a solvent such as isopropanol for a certain period of time. Here, the molar ratio of the oxyranyl group or oxetanyl group of compounds (a) and (b) to the amino group of compound (c) is preferably 1 or more, more preferably 1.1 or more, even more preferably 1.2 or more, and also preferably 4 or less, more preferably 3.9 or less, and even more preferably 3.8 or less.
[0142] Component (F) may include those with the INCI name polysilicone-29, and an example of a commercially available product is Silsoft CLX-E from Momentive Performance Materials (15% by mass of active ingredient, containing dipropylene glycol and water).
[0143] The content of component (F) in the surface finishing agent is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.10% by mass or more, and even more preferably 0.20% by mass or more, from the viewpoint of providing sufficient hydrophobicity to the naturally derived fibers, and from the viewpoint of not giving a sticky feeling, it is preferably 15.00% by mass or less, more preferably 10.00% by mass or less, even more preferably 8.00% by mass or less, and even more preferably 6.00% by mass or less.
[0144] [pH adjuster] The pH of the surface finishing agent at 25°C is preferably within the following ranges from the viewpoint of increasing the reaction rate of the trialkoxysilane portion of component (F) in the acidic or basic range. When the surface finishing agent is in the acidic range, it is preferably 1.0 or higher, more preferably 1.5 or higher, even more preferably 2.0 or higher, preferably 5.0 or lower, more preferably 4.0 or lower, and even more preferably 3.5 or lower. When the surface finishing agent is in the basic range, it is preferably 7.0 or higher, more preferably 7.5 or higher, even more preferably 8.0 or higher, preferably 11.0 or lower, more preferably 10.5 or lower, and even more preferably 10.0 or lower. To adjust the pH of the surface finishing agent to the above ranges, the surface finishing agent may contain a pH adjusting agent as appropriate. As pH adjusters, alkaline agents such as alkanolamines or their salts, including monoethanolamine, isopropanolamine, 2-amino-2-methylpropanol, and 2-aminobutanol; alkanediamines or their salts, including 1,3-propanediamine; carbonates such as guanidine carbonate, sodium carbonate, potassium carbonate, sodium bicarbonate, and potassium bicarbonate; and hydroxides such as sodium hydroxide and potassium hydroxide can be used. As acidic agents, inorganic acids such as hydrochloric acid and phosphoric acid, hydrochloride salts such as monoethanolamine hydrochloride, phosphates such as monopotassium dihydrogen phosphate and disodium monohydrogen phosphate, and organic acids such as lactic acid and malic acid can be used.
[0145] The amount of surface finishing agent used to immerse the natural fibers is preferably 2 or more, more preferably 5 or more, even more preferably 10 or more, and also preferably 100 or less, more preferably 50 or less, and even more preferably 20 or less, in terms of the bath ratio (mass of surface finishing agent / mass of natural fibers) relative to the mass of the natural fibers.
[0146] (Post-heating: Heat treatment to further improve fiber elasticity (toughness)) Furthermore, from the viewpoint of more effectively improving the elasticity of natural fibers, natural fibers can be heated while being stretched under tension. For small quantities of natural fibers, it is preferable to use a hair iron for this heating, and for large quantities, equivalent results can be obtained by applying tension with a winding machine while heating with hot air.
[0147] The fiber stretch rate during heating is preferably 0.1% or more, more preferably 0.2% or more, and even more preferably 0.5% or more, from the viewpoint of more effectively improving the elasticity of the fibers, and from the viewpoint of suppressing damage to the fibers, it is preferably 10% or less, more preferably 5% or less, and even more preferably 2% or less.
[0148] The heating temperature is preferably 120°C or higher, more preferably 140°C or higher, and even more preferably 160°C or higher, from the viewpoint of more effectively improving the elasticity of the fibers, and preferably 240°C or lower, more preferably 220°C or lower, and even more preferably 200°C or lower, from the viewpoint of suppressing damage to the fibers.
[0149] The heating time is preferably 1 second or more, more preferably 3 seconds or more, and even more preferably 5 seconds or more, from the viewpoint of more effectively improving the elasticity of the fibers, and from the viewpoint of suppressing damage to the fibers, it is preferably 60 seconds or less, more preferably 30 seconds or less, and even more preferably 20 seconds or less.
[0150] After heating, the natural fibers can be subjected to tension and stretched while being left to stand in water, in order to more effectively improve their elasticity.
[0151] The elongation rate in this case is preferably 0.1% or more, more preferably 0.2% or more, and even more preferably 0.5% or more, from the viewpoint of more effectively improving the elasticity of the fibers, and preferably 10% or less, more preferably 5% or less, and even more preferably 2% or less, from the viewpoint of suppressing damage to the fibers.
[0152] From the viewpoint of more effectively improving the elasticity of the fibers, the water temperature is preferably 5°C or higher, more preferably 20°C or higher, and even more preferably 30°C or higher. Furthermore, from the viewpoint of suppressing damage to the fibers, the water temperature is preferably 80°C or lower, more preferably 60°C or lower, and even more preferably 50°C or lower.
[0153] The standing time in water is preferably 1 minute or more, more preferably 5 minutes or more, and even more preferably 30 minutes or more, from the viewpoint of more effectively improving the elasticity of the fibers, and from the viewpoint of suppressing damage to the fibers, it is preferably 48 hours or less, more preferably 24 hours or less, and even more preferably 3 hours or less.
[0154] This process, depending on the polymerization conditions in steps (i) to (iii), can result in a fiber that exhibits elasticity comparable to human hair during drying.
[0155] By processing natural fibers as described above, it is possible to manufacture fibers for headwear products that have excellent shape retention and tensile modulus, and significantly improve the elasticity (toughness) of natural fibers, by incorporating condensates formed from components (A) and (B) within the fibers. Furthermore, wigs can be manufactured using these fibers. In this invention, examples of headwear products include hair wigs, hairpieces, weaving, hair extensions, braided hair, hair accessories, doll hair, and the like.
[0156] With respect to the embodiments described above, preferred embodiments of the present invention are further disclosed below.
[0157] <1> A fiber treatment agent containing a condensate formed from the following components (A) and (B), and component (C), wherein the total content of components derived from component (A) and components derived from component (B) is greater than 1% by mass, and the turbidity is 1000 NTU or less. (A): Formaldehyde or its hydrate (B): Triazine derivative represented by general formula (1)
[0158] [ka]
[0159] [In the formula, R 1 ~R 3 These may be the same or different and represent a hydrogen atom, a hydroxymethylamino group, an amino group, a hydroxyl group, a halogen atom, a phenyl group, a linear or branched alkyl or alkenyl group having 1 to 6 carbon atoms, or a linear or branched alkoxy or alkenyloxy group having 1 to 6 carbon atoms. (C):Water
[0160] <2> The content of components derived from component (A) in the fiber treatment agent is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 1.5% by mass or more, even more preferably 3% by mass or more, even more preferably 5% by mass or more, and also preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less, even more preferably 35% by mass or less, and even more preferably 30% by mass or less. <1> The fiber treatment agent described above.
[0161] <3> Component (B) is preferably at least one selected from melamine, monomethylolmelamine, dimethylolmelamine, trimethylolmelamine, benzoguanamine, acetoguanamine, 2,4-diamino-1,3,5-triazine, ammeline, and 2-chloro-4,6-diamino-1,3,5-triazine, more preferably at least one selected from melamine, monomethylolmelamine, dimethylolmelamine, and trimethylolmelamine, and even more preferably melamine. <1> or <2> The fiber treatment agent described above.
[0162] <4> The content of components derived from component (B) in the fiber treatment agent is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 2.5% by mass or more, even more preferably 5% by mass or more, and also preferably 60% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less, even more preferably 35% by mass or less, and even more preferably 30% by mass or less. <1> ~ <3> A fiber treatment agent as described in any one of the items.
[0163] <5> The total content of components derived from component (A) and components derived from component (B) in the fiber treatment agent is preferably 2.5% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more, and also preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 60% by mass or less, even more preferably 50% by mass or less, and even more preferably 40% by mass or less. <1> ~ <4> A fiber treatment agent as described in any one of the items.
[0164] <6> The molar ratio (A) / (B) of components derived from component (A) to components derived from component (B) is preferably 0.005 or more, more preferably 0.01 or more, even more preferably 0.05 or more, even more preferably 0.1 or more, and also preferably less than 5, more preferably 4 or less, even more preferably 3 or less, and even more preferably 2 or less. <1> ~ <5> A fiber treatment agent as described in any one of the items.
[0165] <7> The content of the condensate formed from components (A) and (B) is preferably more than 1% by mass, more preferably 1.5% by mass or more, even more preferably 2.5% by mass or more, even more preferably 5% by mass or more, even more preferably 10% by mass or more, and also preferably 80% by mass or less, more preferably 70% by mass or less, even more preferably 60% by mass or less, even more preferably 50% by mass or less, and even more preferably 40% by mass or less. <1> ~ <6> A fiber treatment agent as described in any one of the items.
[0166] <8> (C) Water is used as the medium, and the content of component (C) is preferably 10% by mass or more, more preferably 20% by mass or more, even more preferably 30% by mass or more, even more preferably 40% by mass or more, and also preferably 99% by mass or less, more preferably 97% by mass or less, even more preferably 95% by mass or less, and even more preferably 90% by mass or less. <1> ~ <7> A fiber treatment agent as described in any one of the items.
[0167] <9> Preferably, further containing the following component (D): <1> ~ <8> A fiber treatment agent as described in any one of the items. (D): Hansen's solubility parameter SP value is 16 MPa 1 / 2 Above 40 MPa 1 / 2 The following organic compounds (excluding organic salts and compounds with an aldehyde group and a molecular weight of 150 or less):
[0168] <10> Component (D) is preferably at least one selected from monohydric alcohols, dihydric alcohols, dihydric alcohol derivatives, trihydric or higher polyhydric alcohols, lactams, imidazolidinones, pyrimidinones, lactones, alkylene carbonates, and general-purpose organic solvents; more preferably at least one selected from dihydric alcohols, lactams, and imidazolidinones; and even more preferably at least one selected from diethylene glycol, triethylene glycol, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, and DMDM hydantoin. <9> The fiber treatment agent described above.
[0169] <11> The SP value of Hansen's solubility parameter for component (D) is preferably 35.8 MPa. 1 / 2 More preferably, 34.7 MPa 1 / 2 More preferably, 29.2 MPa 1 / 2 The following, and preferably 17.8 MPa 1 / 2 The above comfort level is 21.1 MPa. 1 / 2 More preferably, 22.0 MPa 1 / 2 That's all. <9> or <10> The fiber treatment agent described above.
[0170] <12> Preferably, further containing a cationic surfactant, <1> ~ <11> A fiber treatment agent as described in any one of the items.
[0171] <13> The cationic surfactant is preferably a monolong-chain alkylquaternary ammonium salt having one C8-C24 alkyl group and three C1-C4 alkyl groups, more preferably the following general formula
[0172] [ka]
[0173] [In the formula, R 4 R is a saturated or unsaturated linear or branched alkyl group having 8 to 22 carbon atoms. 8 -CO-NH-(CH2) m - or R 8 -CO-O-(CH2) m -(R 8 (where m represents an integer from 1 to 4, and R represents a saturated or unsaturated linear or branched alkyl chain having 7 to 21 carbon atoms.) 5 , R 6 and R 7 These independently represent an alkyl group having 1 to 4 carbon atoms, or a hydroxylalkyl group having 1 to 4 carbon atoms, and X - This represents chloride ions, bromide ions, metosulfate ions, or ethosulfate ions. At least one compound selected from those represented by , more preferably at least one selected from cetyltrimethylammonium chloride, myristyltrimethylammonium chloride, behentrimonium chloride, cetyltrimethylammonium bromide, and stearamidopropyltrimonium chloride. <12> The fiber treatment agent described above.
[0174] <14> The content of the cationic surfactant is preferably 0.05% by mass or more, more preferably 0.10% by mass or more, and also preferably 10% by mass or less, more preferably 5% by mass or less. <12> or <13> The fiber treatment agent described above.
[0175] <15> Preferably, it further contains one or more selected from silicone, more preferably from dimethylpolysiloxane and amino-modified silicone. <1> ~ <14> A fiber treatment agent as described in any one of the items.
[0176] <16> The silicone content is preferably 0.1% by mass or more, more preferably 0.2% by mass or more, even more preferably 0.5% by mass or more, and also preferably 20% by mass or less, more preferably 10% by mass or less, and even more preferably 5% by mass or less. <15> The fiber treatment agent described above.
[0177] <17> Preferably, further containing a cationic polymer, <1> ~ <16> A fiber treatment agent as described in any one of the items.
[0178] <18> The content of the cationic polymer is preferably 0.001% by mass or more, more preferably 0.01% by mass or more, even more preferably 0.05% by mass or more, and also preferably 20% by mass or less, more preferably 10% by mass or less. <17> The fiber treatment agent described above.
[0179] <19> The turbidity is preferably 500 NTU or less, more preferably 100 NTU or less, and even more preferably 20 NTU or less. <1> ~ <18> A fiber treatment agent as described in any one of the items.
[0180] <20> The pH is preferably 3.0 or higher, more preferably 3.5 or higher, even more preferably 4.0 or higher, and also preferably 12.0 or lower, more preferably 11.0 or lower, even more preferably 10.0 or lower, and even more preferably 9.0 or lower. <1> ~ <19> A fiber treatment agent as described in any one of the items.
[0181] <21> Preferably for naturally derived fibers, more preferably for fibers extracted from natural plants and animals, or for artificially manufactured fibers using keratin, collagen, casein, soybeans, peanuts, corn, silk waste, or silk fibroin as raw materials, even more preferably for regenerated protein fibers selected from regenerated collagen fibers using collagen as a raw material and regenerated silk fibers using silk fibroin as a raw material, and even more preferably for regenerated collagen fibers. <1> ~ <20> A fiber treatment agent as described in any one of the items.
[0182] <22> A method for producing a fiber treatment agent, comprising heating a composition containing the following components (A) to (C), wherein the sum of the components derived from component (A) and the components derived from component (B) exceeds 1% by mass, until the turbidity becomes 1000 NTU or less. (A): Formaldehyde or its hydrate (B): Condensation product with a triazine derivative represented by general formula (1)
[0183] [ka]
[0184] [In the formula, R 1 ~R 3 These may be the same or different and represent a hydrogen atom, a hydroxymethylamino group, an amino group, a hydroxyl group, a halogen atom, a phenyl group, a linear or branched alkyl or alkenyl group having 1 to 6 carbon atoms, or a linear or branched alkoxy or alkenyloxy group having 1 to 6 carbon atoms. (C):Water
[0185] <23> The heating temperature is preferably 85°C or higher, more preferably 88°C or higher, even more preferably 90°C or higher, and also preferably 120°C or lower, more preferably 115°C or lower, and even more preferably 110°C or lower. <22> A method for producing the fiber treatment agent described above.
[0186] <24> The heating time is preferably 1 minute or more, more preferably 5 minutes or more, and preferably 20 minutes or less, more preferably 15 minutes or less. <22> or <23> A method for producing the fiber treatment agent described above.
[0187] <25> The pH during heating is preferably 7.0 or higher, more preferably 8.0 or higher, even more preferably 9.0 or higher, and also preferably 13.0 or lower, more preferably 12.0 or lower, and even more preferably 11.0 or lower. <22> ~ <24> A method for producing a fiber treatment agent as described in any one of the items.
[0188] <26> The fiber treatment agent is preferably for naturally derived fibers, more preferably for fibers extracted from natural plants and animals, or for artificially produced fibers using keratin, collagen, casein, soybeans, peanuts, corn, silk waste, or silk fibroin as raw materials, even more preferably for regenerated protein fibers selected from regenerated collagen fibers using collagen as a raw material and regenerated silk fibers using silk fibroin as a raw material, and even more preferably for regenerated collagen fibers. <22> ~ <25> A method for producing a fiber treatment agent as described in any one of the items.
[0189] <27> A fiber processing method including the following step (i). (i) <1> ~ <21> A process of immersing fibers in a fiber treatment agent described in any one of the items, while maintaining a state in which the turbidity of the treatment agent is 1000 NTU or less.
[0190] <28> Preferably, the following step (0) is performed before step (i). <27> The fiber processing method described above. (0) A step of heating the fiber treatment agent.
[0191] <29> If T is defined as the heating time in step (0) from heating the prepared treatment agent, which has a turbidity of 1000 NTU or less, until the turbidity of the treatment agent exceeds 1000 NTU, then the heating time in step (0) is preferably 0.2T or more, more preferably 0.3T or more, even more preferably 0.4T or more, and also preferably 0.8T or less, more preferably 0.7T or less, and even more preferably 0.6T or less. <28> The fiber processing method described above.
[0192] <30> In step (i), the amount of fiber treatment agent used to immerse the fibers is preferably 2 or more, more preferably 3 or more, even more preferably 5 or more, even more preferably 10 or more, even more preferably 20 or more, and also preferably 500 or less, more preferably 250 or less, even more preferably 100 or less. <27> ~ <29> A fiber processing method described in any one of the items.
[0193] <31> The temperature of the fiber treatment agent in step (i) is preferably 20°C or higher, more preferably 35°C or higher, even more preferably 45°C or higher, and also preferably less than 100°C, more preferably 80°C or lower, even more preferably 70°C or lower, and even more preferably 60°C or lower. <27> ~ <30> A fiber processing method described in any one of the items.
[0194] <32> In step (i), the immersion time is preferably 0.3T or more, more preferably 0.4T or more, even more preferably 0.5T or more, and also preferably 0.95T or less, more preferably 0.90T or less, and even more preferably 0.85T or less, when T is defined as the heating time from heating the prepared treatment agent, which has a turbidity of 1000 NTU or less, until the turbidity of the treatment agent exceeds 1000 NTU. <27> ~ <31> A fiber processing method described in any one of the items.
[0195] <33> Preferably, step (i) is followed by step (ii), and steps (i) and (ii) are repeated two or more times. <27> ~ <32> A fiber processing method described in any one of the items. (ii) The process of removing the fibers from the treatment agent before the turbidity of the treatment agent exceeds 1000 NTU.
[0196] <34> Preferably, the following step (iii) is performed after step (ii). <33> The fiber processing method described above. (iii) The process of rinsing the extracted fibers
[0197] <35> Preferably, the rinsing in step (iii) is performed using a rinsing composition containing component (D). <34> The fiber processing method described above. (D): Hansen's solubility parameter SP value is 16 MPa 1 / 2 Above 40 MPa 1 / 2 The following organic compounds (excluding organic salts and compounds with an aldehyde group and a molecular weight of 150 or less):
[0198] <36> The rinsing composition contains water in addition to component (D), and the content of component (D) in the rinsing composition is preferably 60% by mass or more, more preferably 80% by mass or more, and even more preferably 95% by mass or more. <35> The fiber processing method described above.
[0199] <37> Preferably, after steps (i) to (iii), the following step (iv) is performed. <27> ~ <36> A fiber processing method described in any one of the items. (iv) A step of immersing the fibers in a post-crosslinking agent containing components (E) and (C). (E): At least one formaldehyde derivative selected from formaldehyde, formaldehyde hydrate, glyoxylic acid, glyoxylic acid hydrate, glyoxylate, glyoxal, glyoxal hydrate, glutaraldehyde, and glutaraldehyde hydrate. (C):Water
[0200] <38> The content of component (E) in the post-crosslinking agent is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, even more preferably 1% by mass or more, and also preferably 60% by mass or less, more preferably 40% by mass or more, and even more preferably 20% by mass or less. <37> The fiber processing method described above.
[0201] <39> The temperature of the post-crosslinking agent is preferably 20°C or higher, more preferably 35°C or higher, even more preferably 45°C or higher, and also preferably less than 100°C, more preferably 80°C or lower, even more preferably 70°C or lower, and even more preferably 60°C or lower. <37> or <38> The fiber processing method described above.
[0202] <40> Preferably, after steps (i) to (iii) or step (iv), the fibers are further immersed in a surface finishing agent containing the following components (F) and (C). <27> ~ <39> A fiber processing method described in any one of the items. (F) Epoxyaminosilane copolymer, which is the reaction product of the following compounds (a) to (d) (a) Polysiloxane having at least two oxyranyl groups or oxetanyl groups (b) Polyether having at least two oxyranyl or oxetanyl groups (c) Aminopropyltrialkoxysilane (d) Compounds selected from the group consisting of the following primary and secondary amines Primary amines: Methylamine, ethylamine, propyleneamine, ethanolamine, isopropylamine, butylamine, isobutylamine, hexylamine, dodecylamine, oleylamine, aniline, aminopropyltrimethylsilane, aminopropyltriethylsilane, aminomorpholine, aminopropyldiethylamine, benzylamine, naphthylamine, 3-amino-9-ethylcarbazole, 1-aminoheptafluorohexane, 2,2,3,3,4,4,5,5,6,6,7,7,8,8,8-pentadecafluoro-1-octaneamine Secondary amines: Methylethylamine, methyloctadecylamine, diethanolamine, dibenzylamine, dihexylamine, dicyclohexylamine, piperidine, pyrrolidinephthalimide, polymeramines (C) Water
[0203] <41> Preferably, component (F) is polysilicone-29. <40> The fiber processing method described above.
[0204] <42> The content of component (F) in the surface finishing agent is preferably 0.01% by mass or more, more preferably 0.05% by mass or more, even more preferably 0.10% by mass or more, even more preferably 0.20% by mass or more, and also preferably 15.00% by mass or less, more preferably 10.00% by mass or less, even more preferably 8.00% by mass or less, and even more preferably 6.00% by mass or less. <40> or <41> The fiber processing method described above.
[0205] <43> The fibers to be processed are preferably naturally derived fibers, more preferably fibers extracted from natural plants and animals, or fibers artificially manufactured using keratin, collagen, casein, soybeans, peanuts, corn, silk waste, or silk fibroin as raw materials, even more preferably regenerated protein fibers selected from regenerated collagen fibers made from collagen and regenerated silk fibers made from silk fibroin, and even more preferably regenerated collagen fibers. <27> ~ <42> A fiber processing method described in any one of the items.
[0206] <44> A method for manufacturing fibers for headgear products, comprising a step of treating fibers by the fiber treatment method according to any one of claims <27> to <43>.
[0207] <45> A method for manufacturing headgear products, comprising a step of treating fibers by the fiber treatment method according to any one of claims <27> to <43>.
[0208] <46> Fibers for headgear products containing a condensate formed from components (A) and (B). (A): Formaldehyde or its hydrate (B): A triazine derivative represented by the general formula (1)
[0209]
Chemical formula
[0210] [In the formula, R 1 ~R 3 may be the same or different and each represents a hydrogen atom, a hydroxymethylamino group, an amino group, a hydroxyl group, a halogen atom, a phenyl group, a linear or branched alkyl or alkenyl group having 1 to 6 carbon atoms, or a linear or branched alkoxy or alkenyloxy group having 1 to 6 carbon atoms. ] <00009These may be the same or different and represent a hydrogen atom, a hydroxymethylamino group, an amino group, a hydroxyl group, a halogen atom, a phenyl group, a linear or branched alkyl or alkenyl group having 1 to 6 carbon atoms, or a linear or branched alkoxy or alkenyloxy group having 1 to 6 carbon atoms.
[0214] <48> A fiber treatment agent containing the following ingredients (A) to (C). (A) Formaldehyde 1.5-30% by mass (B) One or more selected from melamine, monomethylolmelamine, dimethylolmelamine, and trimethylolmelamine, 5-30% by mass (C) Water
[0215] <49> It further contains the following ingredient (D): <45> The fiber treatment agent described above. (D) One or more selected from diethylene glycol, triethylene glycol, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, and DMDM hydantoin, 15-45% by mass
[0216] <50> Preferably for naturally derived fibers, more preferably for fibers extracted from natural plants and animals, or for artificially manufactured fibers using keratin, collagen, casein, soybeans, peanuts, corn, silk waste, or silk fibroin as raw materials, even more preferably for regenerated protein fibers selected from regenerated collagen fibers using collagen as a raw material and regenerated silk fibers using silk fibroin as a raw material, and even more preferably for regenerated collagen fibers. <48> or <49> The fiber treatment agent described above.
[0217] <51> <48> ~ <50> A fiber treatment agent kit comprising a fiber treatment agent described in any one of the items and a post-crosslinking agent containing components (E) and (C) and having a pH of 1.0 to 4.5. (E) Glyoxylic acid or formaldehyde 1-20% by mass (C) Water level
[0218] <52> Preferably, the surface finishing agent further comprises components (F) and (C). <51> The fiber treatment agent kit described above. (F) Polysilicone-29 0.1~15% by mass (C) Water level
[0219] <53> <48> ~ <50> A fiber treatment kit comprising a fiber treatment agent described in any one of the items and a surface finishing agent containing components (F) and (C). (F) Polysilicone-29 0.1~15% by mass (C) Water level [Examples]
[0220] Examples 1-12, Comparative Examples 1-6 The compositions shown in Table 1 were used to treat regenerated collagen fibers according to the following method, and various evaluations were performed. The pH of each composition was measured directly with a pH meter (HORIBA, F-52) at room temperature (25°C). The turbidity of the compositions was measured at room temperature (25°C) by placing the fiber treatment agent directly into a measurement cell (φ25 x 60 mm borosilicate glass) of a digital turbidimeter (AS ONE, model: TB700, measurement method: compliant with ISO 7027 turbidimetry (90°), light source: infrared radiation diode (850 nm), detector: crystalline silicon solar cell module).
[0221] <Processing method; Examples 1-12, Comparative Examples 1-3 (For those with two or more processing steps, the following cycle was repeated a predetermined number of times.)> 1. A 22cm long bundle of 0.5g of regenerated collagen fiber (*) was immersed in a container containing 40g of fiber treatment agent. The container was sealed, and the entire container was immersed in a 50°C water bath (manufacturer: Toyo Seisakusho Co., Ltd. / model number: TBS221FA) and heated for a specified time. The heating time was standardized to approximately 0.8T (T as described above). ※: The regenerated collagen fibers manufactured by Kaneka were purchased in the form of a commercially available extension product, and the fibers were cut out from it and divided into small bundles for use in evaluation. In this evaluation, the extension product was marked as 100% Ultima used as the fiber type, and the brown with color number 3 and straight shape were used. 2. Take out the container containing the hair bundles from the water bath and let it return to room temperature. 3. Take out the hair bundles from the container, immerse them in 50 g of triethylene glycol for 30 seconds, then rinse with running water at 30°C for 30 seconds, foam with the shampoo for evaluation for 60 seconds, rinse with running water at 30°C for 30 seconds, gently squeeze out the moisture with a towel, and then dry the hair bundles while combing with a warm air dryer (manufactured by Tescom, Nobby White NB3000). At this point, the hair bundles remained straight.
[0222] <Treatment method; Comparative Examples 4 and 5> 1. Apply the fiber treatment agent with a predetermined bath ratio (1.5 g for Comparative Example 4 and 1.0 g for Comparative Example 5) to the hair bundles of 0.5 g of regenerated collagen fibers (※) with a length of 22 cm, let them well blend, then put them into a sealed container, and put the whole container into an oven set at 65°C (forced convection dryer with a stainless steel window; manufactured by AS ONE, SOFW - ۴۵۰) and heat for a predetermined time. ※: The regenerated collagen fibers manufactured by Kaneka were purchased in the form of a commercially available extension product, and the fibers were cut out from it and divided into small bundles for use in evaluation. In this evaluation, the extension product was marked as 100% Ultima used as the fiber type, and the brown with color number 3 and straight shape were used. 2. Take out the container containing the hair bundles from the oven and let it return to room temperature. 3. When the hair bundles were taken out of the container, in both Comparative Examples 4 and 5, the hair bundles were covered with turbid opaque white precipitates. Subsequently, the hair bundles were rinsed with running water at 30°C for 30 seconds, foamed with the shampoo for evaluation for 60 seconds, rinsed with running water at 30°C for 30 seconds, gently squeezed out the moisture with a towel, and then dried the hair bundles while combing with a warm air dryer (manufactured by Tescom, Nobby White NB3000). At this point, the hair bundles remained straight.
[0223] <Increase in average elongation at break during fiber tension> As an indicator of the elasticity (toughness) of fibers under tension, the average elongation at break, that is, the percentage of the original fiber length at which break occurs when the fiber is stretched under tension, was evaluated using the average value obtained from multiple fibers (10 fibers). The evaluation was performed using hair bundles immediately after being treated with the above <treatment method>, following the procedure below. 1. Ten fibers were cut from the base of the hair bundle. A 3cm fiber piece was taken from the middle of the base and tip of each fiber, resulting in a total of 10 3cm hair pieces. 2. The fiber samples were placed in a DIA-STRON limited "MTT690 Automatic Fiber Tensile Tester" and automatic measurement was started to determine the average elongation at break when the fibers were wet. A higher value indicates greater elasticity, superior toughness, and superior durability. According to the following formula, the average elongation at break (A%) when fibers are pulled in their untreated state, as cut from a commercially available product, was used as the baseline. The table shows the percentage increase (C%) in the average elongation at break (B%) of the treated hair bundles compared to the untreated state, as indicated in "Percentage increase in average elongation at break [%]". C(%) = B(%) - A(%)
[0224] <Increase in average breaking load during fiber tension> The average breaking load during fiber tensile stress was evaluated using fiber bundles immediately after treatment according to the above-described <treatment method>. The numerical value used was the average of evaluations performed on multiple fibers (10 fibers). The evaluation was carried out according to the following procedure. 1. Ten fibers were cut from the base of the hair bundle. A 3cm fiber piece was taken from the middle of the base and tip of each fiber, resulting in a total of 10 3cm hair pieces. 2. The fiber samples were placed in the DIA-STRON limited "MTT690 Automatic Fiber Tensile Testing Machine" and automatic measurement was started to determine the breaking load when the fiber was stretched while wet. A higher value indicates greater stiffness and resilience, making the fiber more resistant to stretching by external forces and demonstrating superior durability. According to the following formula, the average breaking load (W0(gf)) under tensile strength of the fibers in their untreated state, as cut from a commercially available product, was used as the baseline. The table shows the increase in the average breaking load (W1(gf)) of the treated fiber bundles from the untreated state (Y(gf)) as "Increase in average breaking load under tensile strength [gf]". Y(gf) = W1(gf) - W0(gf)
[0225] <Suppression of shrinkage when using a high-temperature iron> Shrinkage suppression during high-temperature ironing was tested using hair strands immediately after treatment using the above-described <treatment method>. The average value obtained from evaluating multiple fibers (10 strands) was used. The evaluation was performed using the following procedure. 1. Ten fibers were cut from the base of the hair bundle, and the average length of each fiber was recorded (referred to as length L1). These were then bundled together with two hair bundles of 0.5g of untreated regenerated collagen fiber, and the entire bundle was heated 10 times with a flat iron (Miki Electric Industry Co., Ltd. / Model: AHI-938) set to 180℃ at a speed of 5cm / sec. 2. After the ironing process, 10 fibers were taken out, and the average length of each fiber was recorded again (denoted as length L2). 3. The shrinkage rate during high-temperature ironing is defined as S = { 1 - (L2 / L1)} x 100 [%]. The closer S is to 0%, the less shrinkage occurs due to heat, indicating superior heat resistance.
[0226] <Thermal shape memory ability> The thermal shape memory ability was evaluated using hair bundles immediately after being treated with the above-described processing method. If the result of "I: Shape imparting (curl)" was 5% or less, it was considered to have no effect, and no further processing or evaluation was performed. • I: Shaping (curling) 1. A 22cm long bundle of 0.5g of regenerated collagen fiber was wet with 30°C tap water for 30 seconds, then the wet bundle was wrapped around a 14mm diameter plastic rod and secured with a clip. 2. The hair bundles wound around the rod were immersed in a water bath at 60°C (manufacturer: Toyo Seisakusho Co., Ltd. / model number: TBS221FA) and heated for 1 minute. 3. The hair bundles were taken out of the water bath, immersed in water at 25°C for 1 minute, and then returned to room temperature. 4. The hair bundles were removed from the rod, combed through with a comb 3 times, and then hung and photographed from the side.
[0227] (Evaluation criteria) Using the length of the untreated hair bundle as L0 (22 cm) and the length of the treated hair bundle as L, the curl-up rate = the hair bundle length reduction rate (I) (%) obtained according to the following formula was defined as the curl strength. I = [(L0 - L) / L0] × 100
[0228] ·II: Reshaping (Straight) 1. For the hair bundles evaluated by I, after removing tangles by combing, they were slid 6 times at a speed of 5 cm / sec with a flat iron (manufactured by Miki Electric Industry Co., Ltd. / model number: AHI-938) at a measured temperature of 140°C. 2. They were rinsed for 30 seconds with running water at 30°C of tap water, foamed for 60 seconds with an evaluation shampoo, then rinsed for 30 seconds with running water at 30°C of tap water, and towel-dried. 3. They were dried while applying vibration so that the natural shape of the hair emerged (without using a dryer), combed through with a comb, and then hung and visually observed from the side.
[0229] (Evaluation criteria) Using the length of the untreated hair bundle as L0 (22 cm) and the length of the treated hair bundle as L, the straightening rate (ST) (%) obtained according to the following formula was defined as the degree of achievement of straightening. When ST = 100%, the hair bundle is completely straightened. ST = [1 - (L0 - L) / L0] × 100
[0230] <III: Re-reshaping (Curl)> 1. The hair bundles evaluated by II were wetted with tap water at 30°C for 30 seconds, and then the wet hair bundles were wound around a plastic rod with a diameter of 14 mm and fixed with a clip. 2. The hair bundles wrapped around the rod were immersed in a 60°C water bath (manufacturer: Toyo Seisakusho Co., Ltd. / model number: TBS221FA) and heated for 1 minute. 3. Remove the hair bundles from the water bath and immerse them in 25°C water for 1 minute to return them to room temperature. 4. Remove the hair bundle from the rod, comb it through three times, hang it up, and take a photo from the side.
[0231] (Evaluation Criteria) Let L0 be the length of the untreated hair bundle (22 cm) and L be the length of the treated hair bundle. The curl-up rate = hair bundle length reduction rate (I) (%), calculated according to the following formula, was defined as the curl strength. I = [(L0 - L) / L0] × 100
[0232] <Formula for the evaluation shampoo> Ingredients (mass%) Sodium laureth sulfate 15.5 Lauramide DEA 1.5 Sodium benzoate 0.5 EDTA-2Na 0.3 Amount of phosphoric acid to adjust pH to 7 Ion-exchanged water Balance Total 100
[0233] <Good surface texture> For the tactile evaluation, five expert panelists evaluated the smoothness of the hair strands when touched by hand, using the hair strands immediately after the <shape retention> evaluation. The sum of the five panelists' evaluations was used as the final result. (Evaluation Criteria) 5: It has an extremely smooth texture compared to untreated fibers. 4: It has a smoother feel compared to untreated fibers. 3: It has a slightly smoother feel compared to untreated fibers. 2: The texture is the same as untreated fibers. 1: It is rougher and has a less pleasant feel than untreated fibers.
[0234] [Table 1]
[0235] Example 13 (Post-crosslinking treatment) The regenerated collagen fibers treated in Example 5 were then treated with the post-treatment agents shown in Table 2, and various evaluations were performed.
[0236] <Processing method> 1. A 22cm long bundle of 0.5g of regenerated collagen fiber was immersed in a container containing 40g of post-crosslinking agent. The container was sealed, and the entire container was immersed in a water bath at a specified temperature (manufacturer: Toyo Seisakusho Co., Ltd. / model number: TBS221FA) and heated for a specified time. 2. Remove the container containing the hair bundles from the water bath and allow them to return to room temperature. 3. Remove the hair strands from the container, rinse with 30°C running tap water for 30 seconds, lather with the evaluation shampoo for 60 seconds, rinse again with 30°C running tap water for 30 seconds, lightly towel dry, and then dry the hair strands with a warm air dryer (Tescom Nobby White NB3000) while combing. At this point, the hair strands remained straight.
[0237] [Table 2]
[0238] Example 14 (Surface finishing treatment) The regenerated collagen fibers treated in Example 5 were then treated with the surface finishing agents shown in Table 3, and various evaluations were performed.
[0239] <Processing method> 1. The hair bundle was immersed in a container containing 40g of surface finishing agent and left to stand at room temperature for 30 minutes. 2. Remove the hair bundles from the container and dehydrate them for 5 minutes using a household centrifugal dehydrator (Powerful Spin Dry APD-6.0 ultra-high-speed dehydrator / Alumis Co., Ltd.) (spin coating method). 3. The hair bundles were removed from the spin dryer and heated for 3 hours in an oven set to 60°C (forced convection dryer with stainless steel window; manufactured by AS ONE, SOFW-450). 4. Remove the hair bundle from the oven and let it return to room temperature. 5. Rinse the hair strands in 30°C running water for 30 seconds, lightly towel dry, and then dry the hair strands with a warm air dryer (Tescom Nobby White NB3000) while combing.
[0240] [Table 3]
[0241] Examples 15-18 After processing in Examples 1 and 10, the regenerated collagen fiber bundles were slid 30 times at a speed of 5 cm / sec using a flat iron (manufactured by Miki Electric Industry Co., Ltd. / model number: AHI-938) at a measured temperature of 160°C, and then various evaluations were performed (Examples 15 and 17). Furthermore, the hair bundles after the ironing treatment described above were subjected to various evaluations (Examples 16 and 18). In order to apply tension such that each fiber constituting the hair bundle was stretched by an average of 0.1 to 0.5%, both ends of the hair bundle were pinched with bobby pins and pulled, and the hair bundles were then placed in 40°C water for 1 hour while the bobby pins were secured to the wall of a water bath with tape, and then dried with a hairdryer.
[0242] [Table 4]
[0243] Furthermore, the hair bundles processed in the above embodiments can all be used as extensions by securing them to the hair with pins or the like, and can perform adequately on a human head.
Claims
1. A fiber treatment agent comprising a condensate formed from the following components (A) and (B), and a component (C), in which the total content of components derived from component (A) and components derived from component (B) exceeds 1 mass%, and the turbidity is 1000 NTU or less. (A): Formaldehyde or its hydrate (B): Triazine or its derivative represented by the general formula (1) 【Chemistry 1】 [In the formula, R 1 ~R 3 may be the same or different and represent a hydrogen atom, a hydroxymethylamino group, an amino group, a hydroxyl group, a halogen atom, a phenyl group, a linear or branched alkyl or alkenyl group having from 1 to 6 carbon atoms, or a linear or branched alkoxy or alkenyloxy group having from 1 to 6 carbon atoms. (C):Water
2. 2. The fiber treating agent according to claim 1, wherein the content of the constituent elements derived from component (A) in the fiber treating agent is 0.1% by mass or more and 60% by mass or less.
3. 3. The fiber treating agent according to claim 1, wherein the content of the constituent elements derived from component (B) in the fiber treating agent is 0.1% by mass or more and 60% by mass or less.
4. The fiber treatment agent according to any one of claims 1 to 3, wherein the total content of the components derived from component (A) and the components derived from component (B) in the fiber treatment agent is more than 1 mass% and not more than 80 mass%.
5. The fiber treatment agent according to any one of claims 1 to 4, wherein the molar ratio (A) / (B) of the components derived from component (A) to the components derived from component (B) is less than 5.
6. The fiber treatment agent according to any one of claims 1 to 5, further comprising the following component (D): (D): Hansen solubility parameter SP value is 16MPa 1 / 2 More than 40MPa 1 / 2 Organic compounds that are:
7. A method for producing a fiber treatment agent, comprising heating a composition containing the following components (A) to (C), in which the total content of components derived from component (A) and components derived from component (B) exceeds 1 mass%, until the turbidity becomes 1000 NTU or less. (A): Formaldehyde or its hydrate (B): A condensation product of triazine or its derivative represented by the general formula (1) 【Chemistry 2】 [In the formula, R 1 ~R 3 may be the same or different and represent a hydrogen atom, a hydroxymethylamino group, an amino group, a hydroxyl group, a halogen atom, a phenyl group, a linear or branched alkyl or alkenyl group having from 1 to 6 carbon atoms, or a linear or branched alkoxy or alkenyloxy group having from 1 to 6 carbon atoms. (C):Water
8. A method for treating fibers, comprising the following step (i): (i) A step of immersing a fiber in the fiber treatment agent according to any one of claims 1 to 6 and treating the fiber while maintaining the turbidity of the treatment agent at 1000 NTU or less.
9. The method for treating fibers according to claim 8, further comprising the step (0) below being carried out prior to the step (i). (0) A process for heating the fiber treatment agent
10. 10. The fiber treatment method according to claim 9, wherein the heating time in step (0) is 0.2T to 0.8T, where T is defined as the heating time from when the treatment agent having a turbidity of 1000 NTU or less immediately after preparation is heated until the turbidity of the treatment agent again exceeds 1000 NTU.
11. The method for treating fibers according to any one of claims 8 to 10, wherein a combination of step (i) and the following step (ii) is carried out one or more times: (ii) Removing the fibres from the treatment before the turbidity of the treatment exceeds 1000 NTU.
12. 12. The method for treating fibers according to claim 11, further comprising the step (iii) below, optionally after the step (ii). (iii) Rinse the extracted fibers.
13. 13. The method of claim 12, wherein the rinsing in step (iii) is carried out with a composition containing component (D). (D): Hansen solubility parameter SP value is 16MPa 1 / 2 More than 40MPa 1 / 2 Organic compounds that are:
14. The method for treating fibers according to any one of claims 8 to 13, further comprising carrying out the following step (iv) after steps (i) to (iii): (iv) immersing the fibers in a post-crosslinking agent containing components (E) and (C). (E): at least one formaldehyde derivative selected from formaldehyde hydrate, glyoxylic acid, glyoxylic acid hydrate, glyoxylate, glyoxal, glyoxal hydrate, glutaraldehyde, and glutaraldehyde hydrate; (C):Water
15. A textile processing method according to any one of claims 8 to 14, further comprising carrying out one or more treatments selected from bleaching and dyeing before or after steps (i) to (iv), or between each of steps (i) to (iv).
16. The method for treating fibers according to any one of claims 8 to 15, further comprising, after steps (i) to (iii) or step (iv), a step of immersing the fibers in a surface finishing agent containing the following components (F) and (C): (F) An epoxyaminosilane copolymer which is a reaction product of the following compounds (a) to (d): (a) A polysiloxane having at least two oxiranyl or oxetanyl groups. (b) Polyethers containing at least two oxiranyl or oxetanyl groups. (c) Aminopropyltrialkoxysilane (d) Compounds selected from the group consisting of the following primary and secondary amines: Primary amines: methylamine, ethylamine, propyleneamine, ethanolamine, isopropylamine, butylamine, isobutylamine, hexylamine, dodecylamine, oleylamine, aniline, aminopropyltrimethylsilane, aminopropyltriethylsilane, aminomorpholine, aminopropyldiethylamine, benzylamine, naphthylamine, 3-amino-9-ethylcarbazole, 1-aminoheptafluorohexane, 2,2,3,3,4,4,5,5,6,6,7,7,8,8,8-pentadecafluoro-1-octanamine Secondary amines: methylethylamine, methyloctadecylamine, diethanolamine, dibenzylamine, dihexylamine, dicyclohexylamine, piperidine, pyrrolidine, phthalimide, polymeric amines (C) Water
17. A fiber processing method according to any one of claims 8 to 16, further comprising a post-heating step of heating the treated fiber while applying tension to stretch it.
18. A method for producing a fiber for a head accessory, comprising a step of treating a fiber by the fiber treatment method according to any one of claims 8 to 17.
19. A method for producing a head accessory, comprising a step of treating fibers with the fiber treatment method according to any one of claims 8 to 17.
20. A fiber for headwear products, comprising a condensate produced from components (A) and (B). (A): Formaldehyde or its hydrate (B): Triazine or its derivative represented by the general formula (1) 【Chemistry 3】 [In the formula, R 1 ~R 3 may be the same or different and represent a hydrogen atom, a hydroxymethylamino group, an amino group, a hydroxyl group, a halogen atom, a phenyl group, a linear or branched alkyl or alkenyl group having from 1 to 6 carbon atoms, or a linear or branched alkoxy or alkenyloxy group having from 1 to 6 carbon atoms.
21. A head accessory product comprising, as a component, a fiber containing a condensate produced from components (A) and (B). (A): Formaldehyde or its hydrate (B): Triazine or its derivative represented by the general formula (1) 【Chemistry 4】 [In the formula, R 1 ~R 3 may be the same or different and represent a hydrogen atom, a hydroxymethylamino group, an amino group, a hydroxyl group, a halogen atom, a phenyl group, a linear or branched alkyl or alkenyl group having from 1 to 6 carbon atoms, or a linear or branched alkoxy or alkenyloxy group having from 1 to 6 carbon atoms.
22. The head accessory product according to claim 21, which is selected from a hair wig, a toupee, a weaving, a hair extension, a braided hair, a hair accessory, and a doll hair.
